Probabilistic chamber-pressure windows for EPB shield tunnelling with dynamic cutterhead–soil interaction and spatially variable soil - Xuejian Chen; Po Cheng; Xingsen Guo; Elton Jian Chen; Rita Leal Sousa (Tunnelling and Underground Space Technology, 2027)

Quantifying geothermal heat loss at the Dayoukeng crater using UAV thermal imaging and comparison with Landsat-derived estimates - Hai-Po Chan; Yu-Chang Chan; Cheng-Wei Sun (Geothermics, 2026)

Modeling of structural planes in unstable rock masses: Based on MCMC parameter inversion and point cloud sweeping technology - Yangfu Liu; Po Cheng; Song Xie; Lizhou Wu (Computers & Geosciences, 2026)

Determination of bearing capacity and failure envelope of helical pile in clay under combined loading - Fei Liu; Kaizhe Shang; Chaofan Liu; Songzhao Qu; Po Cheng; Chao Hou; Yanzhao Yuan; Ruiduo Li (Marine Georesources & Geotechnology, 2026)

Anthropogenic-natural driven coastline expansion in China's mainland: Spatiotemporal dynamics, morphological efficiency and coastal vulnerability assessment - Hua Fang; Zhongfeng Qiu; Qiuming Cheng; Ferdinando Nunziata; Jiajun Feng; Ka Po Wong; Jin Yeu Tsou; Maurizio Migliaccio; Yuanzhi Zhang (Journal of Environmental Management, 2026)

Integrated analysis of PM2.5-bound metals and associated sources to investigate the representativeness of atmospheric PM2.5 data for residential exposure in industrial areas during high PM2.5 seasons - Chien-Cheng Jung; Yi-Jie Chung; Po-Hsuan Shao; Charles C.-K. Chou; Yi-Tang Huang (Environmental Research, 2026)

Enhancing vertical and temporal allocation of freeway traffic emissions to improve air quality modeling in Taiwan - Yi-Ju Lee; Fang-Yi Cheng; Bo-Sheng Huang; Sheng-Po Chen (Environmental Pollution, 2026)

Zwitterionic bias–driven electrolyte design enables dendrite-free zinc batteries via water-decoupled ion transport - Chen-Hsuan Hsu; Yung-Cheng Weng; Yi-Jhen Wang; Syun-Hong Chou; Chun-Yen Lai; Po-Yang Peng; Chun-Chi Chang; Jung-Hao Yang; Ta-Chung Liu (Chemical Engineering Journal, 2026)

Dual modulation of intracellular Ca2+ signaling by hispidulin through endoplasmic reticulum mobilization and extracellular Ca2+ entry in human breast cancer cells - Nai-Yu Wang; Cheng-Chung Chang; Chiang-Ting Chou; Po-Min Chang; Wei-Zhe Liang (Journal of Molecular Histology, 2026)

Oxygen-driven metabolic coupling in the extensive catabolism of leucomalachite green by Sphingobium naphthae: Deciphering the biochemical pathways - Chia-Hong Cheng; Po-Kai Pan; Fan-Hua Nan; Yin-Yu Chen; Yu-Sheng Wu (International Biodeterioration & Biodegradation, 2026)

Magnetic field effects on methane–air combustion and emissions in an optical constant volume combustion chamber - Jhe-Kai Lin; Son Hoang Do; Wei-Cheng Wang; Chun-Hao Chiu; Po-Wei Chen; Thong Duc Hong (Fuel, 2026)

Impact of high-pressure processing on the degradation kinetics and bioactivity of resveratrol - Wen-Chien Lu; Yu-Tsung Cheng; Yung-Jia Chan; Shu-Ju Chen; Yan-Zhen Wu; Zeng-Chin Liang; Po-Hsien Li (Food Chemistry, 2026)

Gut microbiota profiles across intrinsic capacity strata in community-dwelling older adults using full-length 16S rRNA sequencing - Chi-Hsien Huang; I-Cheng Lu; Chi-Wei Lin; Ming-Ta Hsieh; I-Hui Chiang; Po-Hsuan Lai; I-Ting Liu; Jung-Sheng Chen (GeroScience, 2026)

Hybrid photoelectrocatalysts for organic contaminant degradation: Pushing the boundaries of water treatment - Amila Kasun Abeysinghe; Chia-Hung Chen; Wu-Xing Chen; Po-Yen Chien; Iresha Premarathne; Fang-Yu Liang; Po-Jung Huang; Wei-Hsiang Chen; Cheng-Di Dong; Yen-Ping Peng (Journal of Environmental Chemical Engineering, 2026)

Capacitive sensor-based artificial stratum corneum for skin irritating assessment of botanical insect repellent products and a de-irritation formulation - Yun-Hsuan Cheng; Po-Chung Chen; Hung-Yu Chen; Chung-Ting Cheng; Yung-Te Hou; Tzong-Jih Cheng (Food and Chemical Toxicology, 2026)

Role of Crack in Earthquake-Induced Anti-dip Rock Slope Instability: Insights from Shaking Table Test and Numerical Analysis - Po Cheng; Manyu Wang; Lizhou Wu; Yao Hu; Shunping Ren; Xuejian Chen; Yong Liu (Rock Mechanics and Rock Engineering, 2026)

Reconstruction of vegetation-occluded rock point clouds for discontinuity identification - Yangfu Liu; Po Cheng; Taorui Zeng; Yu Wang; Song Xie; Lizhou Wu (Engineering Geology, 2026)

Comparative Online–offline measurement of airborne toxic VOCs for health risk and source identification in an environmental justice community - Hsin-Cheng Hsieh; Yuan-Chang Su; Sheng-Po Chen; Chen-Hsuan Chu; Mei-Hui Tseng; Kuan-Chun Lee; Po-Sheng Tseng; Pei-Hsuan Hsu; Chih-Chung Chang; Chieh-Heng Wang; Jia-Lin Wang (Atmospheric Environment, 2026)

Physical modelling of face stability and ground settlement in EPB shield tunnelling incorporating dynamic cutterhead–soil interaction - Xuejian Chen; Lv Liu; Shunping Ren; Po Cheng; Manman Liu; Yong Liu; Elton Jian Chen (Tunnelling and Underground Space Technology, 2026)

Chronoregulatory and neuroprotective effects of yeast β-glucan against systemic inflammation - Wai-Yin Cheng; Pak-Hei Chan; Po-Lam Chan; Ka-Lung Lam; Nathanael Chun-Him Lai; Yuen-Shan Ho; Wing-Fai Yeung; Ka-Hing Wong; Peter Chi-Keung Cheung; Raymond Chuen-Chung Chang (Carbohydrate Polymers, 2026)

An overview of spatiotemporal variation, chemical characteristics, source apportionment, and potential influential factors of PM2.5 in coastal regions and at islands of East Asia - Po-Hsuan Yen; Wen-Hsi Cheng; Yu-Lun Tseng; Chung-Shin Yuan; Kuo-Cheng Lo; Nian-Jie Li; Jia-Yi Zhao (Atmospheric Research, 2026)

Operational Performance of Aquavoltaics Under Different Stakeholder Cooperation Schemes: Evidence from White Shrimp Aquaculture in Taiwan - Bo-Ying Chen; Po-Lin Huang; Yen-Lung Hou; Farok Afero; Szu-Han Liu; Cheng-Ting Huang (Fishes, 2026)
Aquaculture faces rising climate-change risks, while photovoltaic power generation requires substantial land resources, underscoring the need for multifunctional land use in the energy transition. Aquavoltaics—combining aquaculture with solar power—has emerged, and its success depends on stakeholder cooperation. Using white shrimp aquaculture in Taiwan as a case study, this study examines four cooperation schemes—a sole-investment scheme, a photovoltaic-led leasing scheme, a landowner lease-back scheme, and a separated aquaculture and photovoltaic operation scheme—across six aquavoltaic types. Cost–benefit and data envelopment analyses assess the economic returns and operational efficiency of aquaculture operators and photovoltaic companies under each scheme. The results show that all schemes offer profit potential but differ in efficiency and income distribution. The landowner lease-back scheme is most efficient for aquaculture operators, while photovoltaic companies operate near the efficiency frontier in all schemes. The findings highlight that cooperation design shapes the economic feasibility, efficiency, and livelihood impact of aquavoltaic systems, providing a useful reference for future policy and model design.

Late quaternary eruption history of the Tatun Volcano Group (Taiwan) – new constraints from zircon double-dating and 40Ar/39Ar dating of lava flows in Mt. Shamao - Karl D. Jabagat; Yuan-Hsi Lee; Martin Danišík; Daniel Miggins; Mei-Fei Chu; Yu-Ming Lai; Yun-Chieh Lo; Po-Tsun Lee; Cheng-Horng Lin (Tectonophysics, 2026)

Integrated analysis of PM2.5 chemical characteristics and multi-pollutant health risks in Central Taiwan: Implications for optimizing the air quality health index (AQHI) during the COVID-19 pandemic - Po Jui Chen; Tuan Hung Ngo; Shahzada Amani Room; Yuan Cheng Hsu; Yan Cing Li; Shih Yu Pan; Ta Chih Hsiao; Yu-Cheng Chen; Kai Hsien Chi (Science of The Total Environment, 2026)

Engineering supersaturation for the recovery of lanthanum as lanthanum phosphate via fluidized-bed crystallization - Po-Lin Liao; Thanh Binh Nguyen; Chiu-Wen Chen; Cheng-Di Dong (Journal of Water Process Engineering, 2026)

Impacts of period-specific particulate matter exposure on COPD phenotypes: Rapid lung function decline - Po-Hao Feng; I-Jung Liu; Rachel Chien; Kang-Yun Lee; Kuan-Yuan Chen; Wen-Te Liu; Ying-Ying Chen; Yen-Ling Chen; Kun-Ta Lee; Shu-Chuan Ho; Arnab Majumdar; Jiunn-Horng Kang; et al. (Atmospheric Environment, 2026)

Investigating temporal PM2.5 exposure in relation to rapid lung-function decline among COPD patients: A retrospective study - Kang-Yun Lee; Rachel Chien; Kuan-Yuan Chen; Ying-Ying Chen; Wen-Te Liu; Po-Hao Feng; Kun-Ta Lee; Shu-Chuan Ho; Arnab Majumdar; Jiunn-Horng Kang; Wun-Hao Cheng; I-Jung Liu; et al. (Atmospheric Pollution Research, 2026)

Flexible and compressible thermoelectric foam for temperature–pressure dual sensor - Po-Shen Lin; Meng Li; Yong-Qi Chen; Bo-Xuan Hu; Cheng-Liang Liu; Zhi-Gang Chen (Chemical Engineering Journal, 2026)

Coupled oxygen and nitrogen defect sites in Co-N4-coordinated frameworks facilitate stepwise CO2 methanation - Pin-Yu Liu; Sheng-Xiang Chou; Wei-Tse Sun; Hsin-Han Chen; Cheng-Hung Tsai; Yen-Lin Lai; Yu-Cheng Shao; Chi-Liang Chen; Yu-Ching Huang; Yun-Wei Chiang; Bo-Hong Liu; Chia-Hsin Wang; et al. (Chemical Engineering Journal, 2026)

Atomic-scale CuOx–Fe3O4₋x/TiO2 heterostructures with defect synergy for highly selective and efficient reverse water–gas shift reaction - Po-Wen Cheng; Fa-Chih Pai; Chien-Yi Liu; Chih-Wei Hu; Ching-Yi Chou; Guo-Wei Lee; Chia-Shing Wu; Chun-Hong Kuo; Kuang-Kuo Wang; Po-Chun Chen; Tsan-Yao Chen (Chemical Engineering Journal, 2026)

Deep learning-assisted piezoelectric nanogenerators based on layered SnS2/MoS2 heterostructures for interactive sensing and affective computing applications - Cheng-Tse Lee; Hsin-Yu Kuo; Shih-Min Huang; Chien-Chang Chen; Ying-Chin Chao; I-Chih Ni; Bayu Tri Murti; Chih-Jou Chen; Chih-I Wu; Po-Kang Yang (Chemical Engineering Journal, 2026)

A UAV-based multispectral imaging approach for tea shoots aerial mapping and assessment - Hsin-Cheng Chen; Shiou-Ruei Lin; Po-An Chen; Ta-Te Lin (Precision Agriculture, 2026)

A p53-responsive microRNA-100 released from cardiomyoblasts serves as an early biomarker for acute coronary syndrome - Cheng-I Cheng; Ming-Huei Chou; Kuang-Den Chen; Po-Han Chen; Ying-Hsien Kao (Human Cell, 2026)

High-throughput phytoplankton monitoring and screening of harmful and bloom-forming algae in coastal waters with updated functional screening database - Linus Shing Him Lo; Hongbin Liu; Jian-Wen Qiu; Po Keung Eric Tsang; Zhijun Dai; Jinping Cheng (Marine Pollution Bulletin, 2026)

Association between urinary metabolites of 1,3-butadiene and toluene exposure with kidney function indices in Taiwanese school-aged children living near a petrochemical complex - Po-Keng Cheng; Vinoth Kumar Ponnusamy; Wei-Hong Lin; Jeganathan Chinnadurai; Pei-Chien Tsai; Cai-Yu Chen; Wan-Ting Chang; Po-Chin Huang (Environmental Pollution, 2026)

Isomeric halide engineering of self-assembled hole-selective layers for efficient indoor perovskite photovoltaics - Zhong-En Shi; Yi-Ting Hong; Cheng-Chieh Lu; Po-Cheng Shih; Shih-I Lu; Hsiao-Chi Hsieh; Sie-Rong Li; Yu-Che Lin; Zheng-Xuan Cai; Yan-Duo Lin; Chih-Ping Chen (Chemical Engineering Journal, 2026)

Live GABA-producing and heat-killed probiotic consortium improves sleep and modulates inflammation in an anesthesia- and caffeine-induced sleep disturbance model - Zhen-Shu Liu; Yu-Jie Yang; Cheng-Che Tsai; Yu-Tang Tung; Po-Wen Chen (Food Bioscience, 2025)

Microbial, genetic, and urban drivers of ant invasions - Wei-Jiun Lin; Po-Wei Hsu; Edward L Vargo; Chin-Cheng Scotty Yang (Current Opinion in Insect Science, 2025)

Interplay of plasma-treated BiVO4 photoanode and CoFe metal organic frameworks enabled synergistic photoelectrochemical water splitting - Zhi-Cheng Yan; Min-Ho Lin; Chen-Hao Yeh; Pei-Lun Chen; Jun Song Chen; Po-Hsuan Hsiao; Chia-Yun Chen (Chemical Engineering Journal, 2025)

Associations between female reproductive factors and osteoarthritis in women ≥ 50 years old: An NHANES 1999–2018 analysis of more than 10,000 women - Ling-Yun Cheng; Kuo-Chin Huang; Ying-Chen Lu; Po-Yao Chuang (Immunologic Research, 2025)

Stochastic model predictive control of a 10-MW semi-submersible floating offshore wind turbine: A comparative study with gain-scheduled PI, LQR and MPC controllers - Chien Lun Hou; Wei Yu; Mao Hsiung Chiang; Po Wen Cheng (Ocean Engineering, 2025)

Local collaboration between oxygen vacancy, palladium and platinum trimer triggers exceptional performance in the alkaline fuel cell - Dinesh Bhalothia; Che Yan; Yawei Wu; Jui-Cheng Kao; Yu-Chieh Lo; Haolin Li; Nozomu Hiraoka; Hirofumi Ishii; Yen-Fa Liao; Sheng Dai; Chen-Hao Wang; Alice Hu; et al. (Chemical Engineering Journal, 2025)

Seasonal and structural variability of pyrrolizidine alkaloids in Heliotropium sarmentosum (Lam.) Craven - Chun-Lung Feng; Cheng-Kuo Chen; Po-Cheng Wei; Ya-Chen Yang (Biochemical Systematics and Ecology, 2025)

Spatiotemporal variation and clustered routes of atmospheric speciated mercury transported from the East and West Channels of Taiwan Island to South China Sea - Mei-Yun Xiao; Wen-Hsi Cheng; Yu-Lun Tseng; Po-Hsuan Yen; Chung-Shin Yuan; Jia-Yi Zhao; Ming-Shiou Jeng (Atmospheric Research, 2025)

Realizing practical use of LiNiO2 cathode in halide-based all-solid-state lithium metal batteries - Hsi Chen; Hao-Wen Liu; Yu-Cheng Lu; Pei-Jane Yu; Cheng-Hung Liao; Chun-Chieh Wang; Ting-Shan Chan; Hwo-Shuenn Sheu; Po-Ya Chang; Jeng-Lung Chen; Shu-Chih Haw; Gung-Chian Yin; et al. (Chemical Engineering Journal, 2025)

Chemical characterization and oxidative potential of persistent organic pollutants (POPs) in size-resolved particulate matter across industrial and traffic stations - Shahzada Amani Room; Po Jui Chen; Zhi Yu Chen; Yu Ju Shih; Shih Yu Pan; Yuan-Cheng Hsu; Ta-Chih Hsiao; Yu Chieh Ting; Charless C.-K Chou; Chien-Hou Wu; Kai Hsien Chi (Environmental Research, 2025)

Shaking table tests on the failure behavior of a class of anti-dip bedding rock slopes - Yong Liu; Shunping Ren; Dianqing Li; Po Cheng (Engineering Geology, 2025)

Protecting Migrant Labor Rights in the Distant-Water Fisheries Sector: A Comparative Analysis of the Legal Framework of Three Major Fishing Nations in Eastern Asia - Wen-Hong Liu; Po-Chih Hung; Peter Vandergeest; Azmath Jaleel; Bruno Ciceri; Chih-Cheng Lin (Reviews in Fisheries Science & Aquaculture, 2025)

Polycyclic aromatic hydrocarbon-aryl hydrocarbon receptor signaling regulates chronic inflammation in lung-gut axis - Tzu-Yu Cheng; Ching-Shan Luo; Po-Hao Feng; Kuan-Yuan Chen; Chih-Cheng Chang; Nguyen Van Hiep; Yueh-His Chen; Yun-Kai Yeh; Sheng-Ming Wu (Toxicology and Applied Pharmacology, 2025)

Novel synthesis and application of biochar for controlling release and exposure of mercury in the farmland: From human health risk perspective - Nathan Thadeo Yoashi; Che-Jung Hsu; Ying-Lin Wang; Po-Hui Wu; Zheng-Yei Hseu; Ling-Chu Chien; Hsing-Cheng Hsi (Environmental Research, 2025)

Influence of subway train load on seismic response of twin stacked tunnels using three-directional shaking table test in sand - Yao Hu; Mingming Li; Huayang Lei; Mingshuai Li; Peng Zeng; Xuejian Chen; Po Cheng (Tunnelling and Underground Space Technology, 2025)

Effects of pterostilbene on inducing apoptosis in normal bladder and bladder cancer cells - Chen-Hsun Ho; Chia-Kwung Fan; Yi-Chen Chu; Shih-Ping Liu; Po-Ching Cheng (Tissue and Cell, 2025)

Comparison of microwave-assisted and hot-air-drying method on the physicochemical properties and eating quality of rice bran noodles - Ping-Hsiu Huang; Yu-Tsung Cheng; Wen-Chien Lu; I-Yu Chiu; Chiun-Chung R. Wang; Po- Hsien Li (Food Bioscience, 2025)

Simplified modeling of floating offshore wind farms with shared mooring line configurations - Qi Pan; Wei Yu; Po Wen Cheng (Ocean Engineering, 2025)

Enhancing color conversion of perovskite quantum dot-based micro-light-emitting diodes via electrochemical etching and flow chemistry system - Wen-Tse Huang; Yen-Huei Lin; Po-Yi Tu; Loan Thi Ngo; Wei-Cheng Chen; Kai-Ling Liang; Yen-Hsiang Fang; Chaochin Su; Ru-Shi Liu (Chemical Engineering Journal, 2025)

Synergistic properties of single-component hexagonal iron borate for superior and sustainable photo-Fenton catalysis - Po-Yi Wu; Jing-Cheng Hsu; Tsung-Yueh Lin; Yu-Lun Zhu; Yu-Rong Chang; Pei Yuin Keng (Journal of Environmental Chemical Engineering, 2025)

Nitrogen-doped carbon dots/indium-doped zinc sulfide heterostructures for enhanced photocatalytic seawater splitting - Yu-Cheng Chang; Tzu-Jie Chen; Po-Chun Hsu (Journal of Environmental Chemical Engineering, 2025)

Impact of Coal-Fired Power Plants on Suspended Sediment Concentrations in Coastal Waters - Zhi-Cheng Huang; Po-Chien Lin; Po-Hsun Lin; Shun-Hsing Chuang (Journal of Marine Science and Engineering, 2025)
Many coastal coal-fired power plants utilize seawater flue gas desulfurization (SWFGD) systems, which may pose risks of heavy metal attachment on suspended sediments. Understanding variations in suspended sediment concentration (SSC) is therefore useful for controlling marine pollution. We studied two power plants as examples of discharging SSC using continuous measurement techniques. Monitoring sites at intake and discharge points and the surrounding coastal areas of the power plants was conducted across seasons. The first case study, Linkou Power Plant, is located in a high-SSC region influenced by monsoon winds and wave activity. Results indicate that SSC levels at all the monitoring sites are correlated with environmental factors of wind and wave conditions, with strong positive correlations observed between the intake and discharge points. In contrast, the Dalin Power Plant is located within an international harbor, where the SSC levels are generally low; however, sudden increases in SSC are observed at the intake point due to disturbances from vessel activities. These sudden increases are not evident at the discharge point, suggesting a sink of SSC may occur within the system. These results demonstrate that the two studied power plants have limited effects on the increase in SSC; the SSC in the discharge point is mainly related to the SSC input at the intake point. Effective management of SSC at the intake may help mitigate coastal pollution caused by SSC discharge and reduce the risk of harmful substances adhering to suspended solids in the discharging wastewater.

Determination of pullout capacity for an inclined single-plate helical pile under combined loading in clay - Fei Liu; Po Cheng; Hongnan Lin; Jiangtao Yi; Yu Peng; Jun Hu; Ya-pei Chu (Marine Georesources & Geotechnology, 2025)

Effect of soil arching evolution on tunnel face stability considering spatially variable sandy soils - Xuejian Chen; Yao Hu; Po Cheng; Pei-Pei Fang; Kai Yao (Transportation Geotechnics, 2025)

Enrichment and characterization of foodborne fungal spores by ferric ion-based surface-assisted laser desorption/ionization mass spectrometry - Tzu-Ling Yang; Chih-Wei Chen; Noor Hidayat Abu Bakar; Pin-Chen Pan; Po-Hung Cheng; Yu-Chie Chen (Food Chemistry, 2025)

Safety evaluation of Limosilactobacillus fermentum PS150 for use as a commercial psychobiotic - Li-Hao Cheng; Chien-Chen Wu; Chin-Lin Huang; Yu-Hsuan Wei; Pei-Jun Wen; Shih-Hau Chiu; Chien-Chi Chen; Ching-Ting Lin; Po-Lin Liao (Food and Chemical Toxicology, 2025)

Tides enhance the intensity of upwelling and water temperature oscillations in the cold dome region off northeastern Taiwan - Chia-Ying Ho; Hung-Jen Lee; Po-Chun Hsu; Ren-Chieh Lien; Kai-Ho Cheng (Estuarine, Coastal and Shelf Science, 2025)

Seismic Response and Dynamic Failure Mode of a Class of Bedding Rock Slope Subjected to Freeze–Thaw Cycles - Yong Liu; Po Cheng; Enlong Liu; Jun Hu; Yonggang Cheng; Libin Su (Rock Mechanics and Rock Engineering, 2025)

Large-deformation analyses of seismic landslide runout considering spatially random soils and stochastic ground motions - Shun-Ping Ren; Yang Li; Xue-Jian Chen; Po Cheng; Fei Liu; Kai Yao (Bulletin of Engineering Geology and the Environment, 2025)

α-Glucosidase inhibitory activities of aromatic compounds from the rhizomes of Alpinia galanga - Yueh-Hung Cheng; Po-Chun Chen; Zakhele M. Dlamini; Jia-Wei Li; Bongani S. Dlamini; Yu-Kuo Chen; Chi-I Chang (Medicinal Chemistry Research, 2025)

A Finite Element Analysis Comparing an Additive Manufacturing Lattice-Structured PEEK Implant to a Commercial Ball-and-Socket Design for Cervical Total Disc Replacement - Ming-Kai Hsieh; Fu-Cheng Kao; Yun-Da Li; De-Mei Lee; Hui Jin; Ching-Lung Tai; Tsung-Ting Tsai; Po-Liang Lai; Weng-Pin Chen (Journal of Medical and Biological Engineering, 2025)
Purpose Cervical total disc replacement (TDR) is commonly performed to treat degenerative cervical spondylosis, but it often faces challenges such as implant wear and migration. This study aimed to develop and evaluate a novel 3D-printed TDR featuring a titanium endplate and a lattice-structured poly-ether-ether-ketone (PEEK) design. The primary objective was to replicate the natural motion of the cervical disc while addressing complications associated with conventional TDRs. Methods The novel implant was created using additive manufacturing techniques, incorporating three lattice-structured PEEK designs (Cross, Octet, and Ventiles) for the nucleus pulposus and annulus fibrosus components. A finite element analysis was conducted to compare the biomechanical performance of the novel TDR with an intact cervical disc and a commercially available TDR (Baguera®C, Spineart SA, Geneva, Switzerland). Key parameters, including maximal von Mises stresses, range of motion, paths of the instantaneous center of rotation, and facet joint stresses, were evaluated under physiological loads (100 N follower load and 1.5 Nm pure moments). Results The novel 3D-printed TDR maintained structural integrity, with stresses remaining within the yield strength of PEEK. The biomechanical performance closely resembled that of an intact cervical disc, demonstrating similar ranges of motion, instantaneous center of rotation paths, and facet joint stress distributions. Conclusion The findings indicate that the innovative 3D-printed TDR may restore normal cervical spinal kinematics more effectively than existing commercial options, potentially reducing the risk of post-operative facet joint syndrome. Further experimental and clinical studies are recommended to validate these results.

Experimental study on dynamic response and failure mode of bedding rock slope with cracks under earthquake - Po Cheng; Yong Liu; Jun Hu; Kun Fang; Yao Hu (Bulletin of Engineering Geology and the Environment, 2025)

Corrigendum to “Hydrogen peroxide as a mitigation against Microcystis sp. Bloom” [Aquaculture, Volume 577, 15 December 2023, 739932] - Pok Him Ng; Tzu Hsuan Cheng; Ka Yan Man; Liqing Huang; Ka Po Cheng; Kwok Zu Lim; Chi Ho Chan; Maximilian Ho Yat Kam; Ju Zhang; Ana Rita Pinheiro Marques; Sophie St-Hilaire (Aquaculture, 2025)

Rate performance enhancement in lithium-ion batteries using TiNb2-xAlxO7 anodes with self-generated protective layers - Jia-Hui Wang; Tanmoy Paul; Prem Chandan; Suhendro Purbo Prakoso; Po-Wei Chi; Kuo-Wei Yeh; Chung-Chieh Chang; Maw-Kuen Wu; Yu-Cheng Chiu (Chemical Engineering Journal, 2025)

Investigation of the abasic sites induced by hydrogen peroxide and methyl methanesulfonate in calf thymus DNA and BEAS-2B cells - Dat Thanh Dinh; Gilang Putra Bahari; Qi Xu; Cheng-Hao Wei; Dar-Ren Chen; Wei-Chung Hsieh; Po-Hsiung Lin (Toxicology Letters, 2024)

Effect of soil spatial variability on the stability of pipelines under horizontal loading - Fei Liu; Po Cheng; Zhen Wang; Jiang Tao Yi; Xue-jian Chen; Yu Peng; Kai Yao; Jun Hu (Computers and Geotechnics, 2024)

Gel electrolyte design for nonflammable lithium-ion batteries with high-rate and high-voltage characteristics - Po-Wei Huang; Qin-Cheng Zhang; Ming-Yuan Hung; Yan-Cheng Lin; Hong-Kang Tian; Yuh-Lang Lee; Jeng-Shiung Jan; Hsisheng Teng (Chemical Engineering Journal, 2024)

Rapid green analytical methodology for simultaneous monitoring of nitrosamines and semi-volatile organic compounds in water and human urine samples - Shih-Tao Hu; Uday Shashikumar; Swapnil Gurrani; Yu-Tung Tseng; Karthikeyan Prakasham; Cheng-Te Huang; Anbarasu Krishnan; Chao-En Wang; Po-Chin Huang; Vinoth kumar Ponnusamy (Environmental Geochemistry and Health, 2024)

Advances in perfluoro-alkylated compounds (PFAS) detection in seafood and marine environments: A comprehensive review on analytical techniques and global regulations - Prasath Ramasamy Chandrasekaran; Jeganathan Chinnadurai; Yee Cheng Lim; Chiu-Wen Chen; Pei-Chien Tsai; Po-Chin Huang; Mohsen Gavahian; Gangadhar Andaluri; Cheng-Di Dong; Yuan-Chung Lin; Vinoth Kumar Ponnusamy (Environmental Geochemistry and Health, 2024)

Chemical characteristics and formation mechanism of secondary inorganic aerosols: The decisive role of aerosol acidity and meteorological conditions - Yu-Chieh Ting; Chuan-Hsiu Huang; Yu-Hsiang Cheng; Ta-Chih Hsiao; Webber Wei-Po Lai; Zih-Jhe Ciou (Environmental Pollution, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Mechanical properties and micromechanics of graphene oxide modified calcareous sand-cement mortar - Jun Hu; Chenming Xu; Po Cheng; Hui Xiong; Yuxuan Zhou; Junhao Ren (Marine Georesources & Geotechnology, 2024)

The Impact of Coal-Fired, Soot on China's Industrial Production and Total Factor Energy Efficiency - Zhihuan Xu; Taisheng Zhang; Lei Zhuang; Po-Feng Wu; Ching-Cheng Lu (Water, Air, & Soil Pollution, 2024)

Design and assessment of highly stable norfloxacin/ Ca-montmorillonite (STx-1b) as oral beads - Po-Hsiang Chang; Chenxing Liang; Yating Yang; Yaqi Wen; Cheng-I Lee; Juin-Yen Ho; Chien-Yen Chen; Yu-Min Tzou (Applied Clay Science, 2024)

Improvement of the Diagnostic Method for the Detection of Parasite Eggs Using the Formalin Ethyl Acetate Concentration Technique - Jia-Hung Liou; Te-Ling Lu; Hui-Fen Cheng; Long-Wei Lin; Po-Cheng Kung; Hong-Jing Chuang; Te-Hsiu Lee; Chee-Hong Chan; Te-Jung Lu (Acta Parasitologica, 2024)

Optimization of biological nitrogen removal in full-scale municipal WWTPs using activated sludge model simulation - Hai-Hsuan Cheng; Po-Wei Huang; Liang-Ming Whang (Chemosphere, 2024)

Predicting ischemic stroke patients’ prognosis changes using machine learning in a nationwide stroke registry - Ching-Heng Lin; Yi-An Chen; Jiann-Shing Jeng; Yu Sun; Cheng-Yu Wei; Po-Yen Yeh; Wei-Lun Chang; Yang C. Fann; Kai-Cheng Hsu; Jiunn-Tay Lee (Medical & Biological Engineering & Computing, 2024)
Accurately predicting the prognosis of ischemic stroke patients after discharge is crucial for physicians to plan for long-term health care. Although previous studies have demonstrated that machine learning (ML) shows reasonably accurate stroke outcome predictions with limited datasets, to identify specific clinical features associated with prognosis changes after stroke that could aid physicians and patients in devising improved recovery care plans have been challenging. This study aimed to overcome these gaps by utilizing a large national stroke registry database to assess various prediction models that estimate how patients’ prognosis changes over time with associated clinical factors. To properly evaluate the best predictive approaches currently available and avoid prejudice, this study employed three different prognosis prediction models including a statistical logistic regression model, commonly used clinical-based scores, and a latest high-performance ML-based XGBoost model. The study revealed that the XGBoost model outperformed other two traditional models, achieving an AUROC of 0.929 in predicting the prognosis changes of stroke patients followed for 3 months. In addition, the XGBoost model maintained remarkably high precision even when using only selected 20 most relevant clinical features compared to full clinical datasets used in the study. These selected features closely correlated with significant changes in clinical outcomes for stroke patients and showed to be effective for predicting prognosis changes after discharge, allowing physicians to make optimal decisions regarding their patients’ recovery. Graphical Abstract

Capnesterones A and B, new steroids isolated from the soft coral Capnella imbricata - Ting-Yu Cheng; Chia-Jung Yang; Po-Jen Chen; Yu-Li Chen; Bo-Rong Peng; Te-An Kung; Zhi-Hong Wen; Kuei-Hung Lai; Hsu-Ming Chung (Phytochemistry Letters, 2024)

Physicochemical properties of Dioscorea alata Tainung No. 1 and 2 via different drying methods and application on the frozen tangyuan - Ping-Hsiu Huang; Yu-Tsung Cheng; Shu-Ju Chen; Wen-Chien Lu; Po-Yuan Chiang; Wen-Pei Cheng; Chiun-Chuang R. Wang; Po-Hsien Li (Food Bioscience, 2024)

Effects of Vitamin D Supplementation on Cognitive Outcomes: A Systematic Review and Meta-Analysis - Wen-Yin Chen; Ying-Chih Cheng; Chih-Chiang Chiu; Hsing-Cheng Liu; Ming-Chyi Huang; Yu-Kang Tu; Po-Hsiu Kuo (Neuropsychology Review, 2024)

In-situ and label-free measurement of cytochrome C concentration with a Ti2C-MXene sensitized fiber-optic MZI sensor - Po Jin; Ya-nan Zhang; Zhong Li; Wanlu Zheng; Liangliang Cheng; Like Li; Xuegang Li; Yong Zhao (Analytica Chimica Acta, 2024)

A shift in the host web occupancy of dew‐drop spiders associated with genetic divergence in the Southwest Pacific - Noraya U. Elias; Mae A. Responte; Cheng‐Yu Wu; Yi‐Fan Chiu; Po Peng; Hauchuan Liao; Rafe M. Brown; Yong‐Chao Su (Journal of Biogeography, 2024)
Aim We assessed the population genetic structure of the kleptoparasitic spider Argyrodes bonadea across the Southwestern Pacific islands. Our aim is to evaluate the impact of overseas distances and, in particular, the Kerama gap, as potential drivers of genetic differentiation. If no relationship exists, then we assume dispersal following adaptive change as alternative non‐vicariant mechanism that generates divergence. Location Southwestern Pacific Islands. Taxon Argyrodes bonadea. Methods We used mitochondrial Cytochrome Oxidase 1 (CO1) gene sequences and Restriction Site‐associated DNA Sequencing (RAD‐seq) for our analyses. Results Two strongly supported lineages, an Amami‐Okinawa Lineage (AOL) and an Austral‐Asia Lineage (AAL), correspond to two separate clades, roughly divided by the Kerama Gap, in phylogenetic trees estimated here. However, species delimitation led to the interpretation of only a single species present. The AOL exhibits complex, geographically structured host web spider species specificity, wherein the Amami population utilizes Cyrtophora , but AOL samples in Okinawa associate exclusively with Nephila —and yet all broadly distributed AAL populations show no evidence of host web spider species specificity. Main Conclusion The population boundary between AOL and AAL likely results from local adaptation to novel hosts—instead of isolation by the Kerama Gap—following long‐distance dispersal and range expansion. Our results suggest kleptoparasitic spiders have the capacity to overcome permanent deep‐sea barriers and colonize distant landmasses. Whereas peripheral populations (AOL) demonstrate the capacity for specialization to a single host, which may have contributed to genetic differentiation and isolation, the broadly distributed AAL persists and has successfully expanded its geographical range as a host generalist, which may contribute to ongoing gene flow inferred in this study.

A New Perspective on the Semi-quantitative Meso-structural Failure Mechanism of Deep Weak Interlayer Zone Under Different Stress Paths - Shu-Qian Duan; Po Gao; Ding-Ping Xu; Bei Cao; Guo-feng Liu; Quan Jiang; Shi-Li Qiu; Jie-Cheng Xiong (Rock Mechanics and Rock Engineering, 2024)

Health assessment of emerging persistent organic pollutants (POPs) in PM2.5 in northern and central Taiwan - Shahzada Amani Room; Kai Ting Huang; Shih Yu Pan; Po Jui Chen; Yuam-Cheng Hsu; Kai Hsien Chi (Chemosphere, 2024)

Streamlining regular liquid chromatography with MALDI-TOF MS and NMR spectroscopy using automatic full-contact splitless spotting interface and flash-tap fractioning collection - Chi-Minh Truong; Yung-Cheng Jair; Hong-Po Chen; Wei-Chih Chen; Yi-Hsin Liu; Pin-Chuan Chen; Pai-Shan Chen (Analytica Chimica Acta, 2024)

Identification of potential source regions and long-range transport routes/channels of marine PM2.5 at remote sites in East Asia - Po-Hsuan Yen; Chung-Shin Yuan; Ker-Yea Soong; Ming-Shiou Jeng; Wen-Hsi Cheng (Science of The Total Environment, 2024)

The economic feasibility of aquavoltaics in Taiwan - A case study of whiteleg shrimp (Litopenaeus vannamei) culture - Bo-Ying Chen; Po-Lin Huang; Yen-Lung Hou; Hsun-Yu Lan; Cheng-Ting Huang; Fan-Hua Nan (Aquaculture, 2024)

Ozone containment through selective mitigation measures on precursors of volatile organic compounds - Sheng-Po Chen; Wen-Tzu Liu; Fang-Yi Cheng; Chieh-Heng Wang; Shih-Ming Huang; Jia-Lin Wang (Science of The Total Environment, 2024)

Highly effective photocatalytic degradation of plastic film (LDPE) using Ruthenium-incorporated g-C3N4 via the Norrish mechanism - Lely Ayu Ningsih; Po-Yi Lu; Shu Ashimura; Masaaki Yoshida; Wen-Chang Chen; Yu-Cheng Chiu; Chechia Hu (Chemical Engineering Journal, 2024)

The Bioeconomic Analysis of Hybrid Giant Grouper (Epinephelus fuscoguttatus × Epinephelus lanceolatus) and Green Grouper (Epinephelus malabaricus): A Case Study in Taiwan - Po-Lin Huang; Farok Afero; Yao Chang; Bo-Ying Chen; Hsun-Yu Lan; Yen-Lung Hou; Cheng-Ting Huang (Fishes, 2023)
Grouper aquaculture is a rapidly growing and dynamic industry within the Taiwan aquaculture sector that serves as an important source of income generation. Farming fishes at a better location (FFABL) is a promising production strategy. This study evaluated the production and economic performance of grouper farming in Taiwan. This investigation employed two steps: (1) a cost–benefit analysis to determine the main component affecting profitability; and (2) multivariate statistics to clarify the relationship between biological and economic factors. The findings suggest that the best choice of species is hybrid giant grouper that generates and highlights a positive income, viable benefit–cost ratio and profit rate. The study found the feed management of hybrid giant groupers requires more consideration due to its low feed conversion ratio. The producers need to replace trash fish in commercial feed during the production cycle to ensure better feed management. Finally, this paper argues that feed is the main constraint for grouper farming, which is sensitive to any change in feed productivity, and this constraint must be solved to sustain the grouper industry in Taiwan.

Hydrogen peroxide as a mitigation against Microcystis sp. bloom - Pok Him Ng; Tzu Hsuan Cheng; Ka Yan Man; Liqing Huang; Ka Po Cheng; Kwok Zu Lim; Chi Ho Chan; Maximilian Ho Yat Kam; Ju Zhang; Ana Rita Pinheiro Marques; Sophie St-Hilaire (Aquaculture, 2023)

Probabilistic investigations on the elastic stiffness coefficients for suction caisson considering spatially varying soils - Po Cheng; Yao Hu; Kai Yao; Yong Fu; Yong Liu (Ocean Engineering, 2023)

Inhibition of continuous cropping obstacle of celery by chemically modified biochar: An efficient approach to decrease bioavailability of phenolic allelochemicals - Chia-Chia Lin; Yu-Ting Liu; Po-Hsiang Chang; Yi-Cheng Hsieh; Yu-Min Tzou (Journal of Environmental Management, 2023)

Insight and mechanisms of tetracycline adsorption on sodium alginate/montmorillonite composite beads - Po-Hsiang Chang; Raj Mukhopadhyay; Binoy Sarkar; Yun-Cheng Mei; Chih-Hsun Hsu; Yu-Min Tzou (Applied Clay Science, 2023)

Cervical spinal epidural abscess secondary to acupuncture: a case report and literature review - Yun-Wen Song; Po-Sung Yang; I-Chin Cheng; Chih-Hsien Hung (Acta Neurologica Belgica, 2023)

Quantifying the potential effects of air pollution reduction on population health and health expenditure in Taiwan - Yi-Hsuan Roger Chen; Wan-Chen Lee; Bo-Chen Liu; Po-Chieh Yang; Chi-Chang Ho; Jing-Shiang Hwang; Tzu-Hsuan Huang; Hsien-Ho Lin; Wei-Cheng Lo (Environmental Pollution, 2023)

Nanoscale photocatalytic hydrogen production system mitigates inflammation by harnessing glycolysis waste - Cheng-Yu Wu; Cam-Hoa Mac; Tung-Han Yang; Khanh Nguyen; Shih-Kai Lo; Yen Chang; Po-Liang Lai; Hsing-Wen Sung; Yu-Jung Lin (Chemical Engineering Journal, 2023)

Numerical investigation on pullout capacity of helical piles under combined loading in spatially random clay - Po Cheng; Jia Guo; Kai Yao; Xuejian Chen (Marine Georesources & Geotechnology, 2023)

Effects of ammonia on combustion of coal in stoichiometric premixed methane–air flames - Yueh-Heng Li; Bo-Cheng Chuang; Po-Hung Lin; Janusz Lasek (Fuel, 2023)

Associations of fine particulate matter exposure with sleep disorder indices in adults and mediating effect of body fat - Cheng-Yu Tsai; Huei-Tyng Huang; Ming Liu; Wun-Hao Cheng; Wen-Hua Hsu; Arnab Majumdar; Kang-Yun Lee; Po-Hao Feng; Chien-Hua Tseng; Kuan-Yuan Chen; Yi-Chun Kuan; Jiunn-Horng Kang; et al. (Atmospheric Pollution Research, 2023)

Exploring promising electron-shuttling characteristics of Perilla frutescens and potential anti-viral activity via bioenergy generation in microbial fuel cells - Po-Wei Tsai; Maria Regina Gean G. Aledia; Kathlia A. De Castro-Cruz; Patrick Jay B. Garcia; Cheng-Jui Shen; Chung-Chuan Hsueh; Chung-Yu Chen; Bor-Yann Chen (Sustainable Chemistry and Pharmacy, 2023)

Minimal addition of transglutaminase on the preparation and characteristics of tilapia (Oreochromis mossambicus) surimi - Ping-Hsiu Huang; Yu-Tsung Cheng; Yung-Jia Chan; Wen-Chien Lu; Wen-Ching Ko; Hung-Chun Hsieh; Po-Hsien Li (Fisheries Science, 2023)

Modeling and validation of a tuned liquid multi-column damper stabilized floating offshore wind turbine coupled system - Wei Yu; Frank Lemmer; Po Wen Cheng (Ocean Engineering, 2023)

Cost-effective and accurate monitoring of flowering across multiple tropical tree species over two years with a time series of high-resolution drone imagery and deep learning - Calvin Ka Fai Lee; Guangqin Song; Helene C. Muller-Landau; Shengbiao Wu; S. Joseph Wright; K.C. Cushman; Raquel Fernandes Araujo; Stephanie Bohlman; Yingyi Zhao; Ziyu Lin; Zounachuan Sun; Peter Chuen Yan Cheng; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Large-deformation modelling of earthquake-triggered landslides considering non-uniform soils with a stratigraphic dip - Shun-Ping Ren; Xue-Jian Chen; Zeng-Le Ren; Po Cheng; Yong Liu (Computers and Geotechnics, 2023)

Multiscale Analysis and Prediction of Sea Level in the Northern South China Sea Based on Tide Gauge and Satellite Data - Yilin Yang; Qiuming Cheng; Jin-Yeu Tsou; Ka-Po Wong; Yanzhuo Men; Yuanzhi Zhang (Journal of Marine Science and Engineering, 2023)
Under the influence of global warming, the problem of sea-level rise is becoming increasingly prominent. The northern part of the South China Sea (SCS) is low lying, with intense economic development, and densely populated. These characteristics make the region extremely sensitive to the consequences of rising sea levels. This study aims to reveal the trends of sea-level changes in the northern SCS and provide scientific insights into the potential flooding risks in low-lying areas. To achieve this, the Ensemble Empirical Mode Decomposition (EEMD) method is used to analyze the water level time series data from three tide gauges along the coast of Hong Kong. This analysis reveals the multidimensional change characteristics and response mechanisms of the sea level in the SCS. The findings reveal distinct seasonal, interannual, decadal, and interdecadal variations in sea-level changes. Furthermore, we explore the impact of the El Niño-Southern Oscillation (ENSO) on sea-level changes in the study area, finding a 6-month lagged correlation between the sea level and ENSO. Spatially, the rate of sea-level change is faster in nearshore areas than in the open ocean and higher in the northern regions than in the southern regions. The Multifractal Detrended Fluctuation Analysis (MF-DFA) method is employed to analyze the sea-level change time series, revealing long-range correlations and multifractal characteristics. In addition, we propose a sea-level prediction method that combines EEMD with Long Short-Term Memory (LSTM) neural networks and conducts empirical research on sea-level changes in the northern South China Sea. The results indicate that the EEMD-LSTM model outperforms the standalone LSTM model in terms of predictive accuracy, effectively eliminating noise from signals and providing a valuable reference. In summary, this research delves into the multiscale characteristics and influencing factors of sea-level changes in the northern SCS, proposing an improved sea-level prediction method that integrates EEMD and LSTM. The findings lay the groundwork for evaluating the risks of sea-level rise in low-lying regions of the northern SCS and inform future response strategies.

Artificial intelligence and visual analytics in geographical space and cyberspace: Research opportunities and challenges - Min Chen; Christophe Claramunt; Arzu Çöltekin; Xintao Liu; Peng Peng; Anthony C. Robinson; Dajiang Wang; Josef Strobl; John P. Wilson; Michael Batty; Mei-Po Kwan; Maryam Lotfian; et al. (Earth-Science Reviews, 2023)

Route-based chemical significance and source origin of marine PM2.5 at three remote islands in East Asia: Spatiotemporal variation and long-range transport - Chung-Shin Yuan; Chung-Min Hung; Kuo-Ning Hung; Zong-Mou Yang; Po-Hung Cheng; Ker-Yea Soong (Atmospheric Pollution Research, 2023)

Identification of Rhodosorus marinus isolated in Taiwan and study on its optimum culture conditions - Wei Qing Chloe Lung; Jane Wungen-Sani; Chi-Cheng Huang; Chien-Li Chen; Hung-Chih Lai; Yeh-Fang Hu; Po-Tsang Lee; Fan-Hua Nan; Han-Yang Yeh; Meng-Chou Lee (Journal of Applied Phycology, 2023)

Evaluation of wetting measures and capture efficiencies of fugitive dust emitted from a limestone pile: Experiments and artificial neural network - Po-Hsuan Yen; Justus Kavita Mutuku; Chung-Shin Yuan; Wei-Hsiang Chen; Chih-Cheng Wu; Chien-Sen Li (Process Safety and Environmental Protection, 2023)

Involvement of microRNA164 in responses to heat stress in Arabidopsis - Wei-An Tsai; Po-Han Sung; Yun-Wei Kuo; Ming-Cheng Chen; Shih-Tong Jeng; Jeng-Shane Lin (Plant Science, 2023)

Effectiveness of Combined Exercise and Physiotherapy Intervention in Improving Functional Activity of Patients with Knee Osteoarthritis in Muslim Pray Movements - Rakhmad Rosadi; Po-Ting Wu; Yu-Lin You; Li-Chieh Kuo; Cheng-Feng Lin (Journal of Medical and Biological Engineering, 2023)

Genetic analysis reveals the putative native range and widespread double‐clonal reproduction in the invasive longhorn crazy ant - Shu‐Ping Tseng; Hugo Darras; Po‐Wei Hsu; Tsuyoshi Yoshimura; Chow‐Yang Lee; James K. Wetterer; Laurent Keller; Chin‐Cheng Scotty Yang (Molecular Ecology, 2023)
Clonal reproduction can provide an advantage for invasive species to establish as it can circumvent inbreeding depression which often plagues introduced populations. The world's most widespread invasive ant, Paratrechina longicornis , was previously found to display a double‐clonal reproduction system, whereby both males and queens are produced clonally, resulting in separate male and queen lineages, while workers are produced sexually. Under this unusual reproduction mode, inbreeding is avoided in workers as they carry hybrid interlineage genomes. Despite the ubiquitous distribution of P. longicornis , the significance of this reproductive system for the ant's remarkable success remains unclear, as its prevalence is still unknown. Further investigation into the controversial native origin of P. longicornis is also required to reconstruct the evolutionary histories of double‐clonal lineages. Here, we examine genetic variation and characterize the reproduction mode of P. longicornis populations sampled worldwide using microsatellites and mitochondrial DNA sequences to infer the ant's putative native range and the distribution of the double‐clonal reproductive system. Analyses of global genetic variations indicate that the Indian subcontinent is a genetic diversity hotspot of this species, suggesting that P. longicornis probably originates from this geographical area. Our analyses revealed that both the inferred native and introduced populations exhibit double‐clonal reproduction, with queens and males around the globe belonging to two separate, nonrecombining clonal lineages. By contrast, workers are highly heterozygous because they are first‐generation interlineage hybrids. Overall, these data indicate a worldwide prevalence of double clonality in P. longicornis and support the prediction that the unusual genetic system may have pre‐adapted this ant for global colonization by maintaining heterozygosity in the worker force and alleviating genetic bottlenecks.

Long-range transport of atmospheric speciated mercury from the eastern waters of Taiwan Island to northern South China Sea - Chung-Shin Yuan; Kuan-Chen Chiang; Po-Hsuan Yen; Jun-Hao Ceng; Cheng-En Lee; I-Chieh Du; Ker-Yea Soong; Ming-Shiou Jeng (Environmental Pollution, 2023)

The role of branched alkylthio side chain on dispersion and thermoelectric properties of regioregular polythiophene/carbon nanotubes nanocomposites - Po-Shen Lin; Shin Inagaki; Jia-Hao Liu; Ming-Chou Chen; Tomoya Higashihara; Cheng-Liang Liu (Chemical Engineering Journal, 2023)

Infusing satellite data into aerosol forecast for near real-time episode detection and diagnosis in East Asia - Sheng-Po Chen; Cheng-Hsuan (Sarah) Lu; James E. Davies; Chang-Feng Ou-Yang; Neng-Huei Lin; Amy K. Huff; Bradley R. Pierce; Shobha Kondragunta; Jia-Lin Wang (Science of The Total Environment, 2023)

Dietary supplementation of synbiotic Leuconostoc mesenteroide B4 and dextran improves immune regulation and disease resistance of Penaeus vannamei against Vibrio parahaemolyticus - Mei-Ying Huang; Chia-Yi Lo; Cheng-Yu Lai; Jong-Ding Yu; Po-Tsang Lee (Fish & Shellfish Immunology, 2023)

Evaluation of LiNiO2 with minimal cation mixing as a cathode for Li-ion batteries - Rio Akbar Yuwono; Fu-Ming Wang; Nae-Lih Wu; Yan-Cheng Chen; Hsi Chen; Jin-Ming Chen; Shu-Chih Haw; Jyh-Fu Lee; Rui-Kun Xie; Hwo-Shuenn Sheu; Po-Ya Chang; Chusnul Khotimah; et al. (Chemical Engineering Journal, 2023)

Intimate interaction of TFSI− anions with MoO3−x oxygen vacancies boost ionic conductivity of cathode-supported solid polymer electrolyte - Rohan Paste; Chintam Hanmandlu; Po-Yu Su; Cheng-Hung Hou; Hsin-An Chen; Chun-Wei Pao; Jing-Jong Shyue; Kuei-Hsien Chen; Heng-Liang Wu; Hong-Cheu Lin; Chih Wei Chu (Chemical Engineering Journal, 2023)

Promoting human rights for Taiwan’s fishermen: Collaboration with the primary source countries of Taiwan’s DWF migrant fishermen - Po-Chih Hung; Hsiao-Chien Lee; Chih-Cheng Lin; Wen-Hong Liu (Frontiers in Marine Science, 2022)
Taiwan is one of the largest distant water fishing (DWF) nations worldwide, and relies largely on the migrant labor to keep costs low. However, this industry has caused Taiwan to be listed in the 2020 “List of Goods Produced by Child Labor or Forced Labor” of the U.S. Department of Labor. In view of this, the Taiwanese government is actively adopting further management measures to supervise the domestic and foreign fishermen agencies. It is because the latter has been involved in many disputes, especially in recruitment, payroll, and labor contracts, which directly or indirectly affect the rights of migrant fishermen. On the other hand, although the C188 Work in Fishing Convention has stregthend the protection of the fishermen’s human rights, it still stays ambiguous in terms of private agency management. That is also why so many disputes have been caused in recent years.This study conducts a comparative analysis of the agency management systems in the primary source countries of Taiwan’s distant water fishing migrant fishermen (that is, Indonesia, the Philippines, and Vietnam), as well as interviews with distant water fishing stakeholders to provide insights on the improvement of agency management and migrant fishermen’s rights in Taiwan. The findings imply that the positive interaction, mutual trust, and understanding of laws and regulations between fishermen’s exporting and importing countries lead to future cross-national collaboration. This study suggests that the Taiwanese government should follow the spirit of the C188 but not be restricted to the Convention texts to amend or formulate regulations and policies of agencies for fully protecting the rights of migrant fishermen.

Mesenchymal Stem Cell Secreted-Extracellular Vesicles are Involved in Chondrocyte Production and Reduce Adipogenesis during Stem Cell Differentiation - Yu-Chen Tsai; Tai-Shan Cheng; Hsiu-Jung Liao; Ming-Hsi Chuang; Hui-Ting Chen; Chun-Hung Chen; Kai-Ling Zhang; Chih-Hung Chang; Po-Cheng Lin; Chi-Ying F. Huang (Tissue Engineering and Regenerative Medicine, 2022)
Background: Extracellular vesicles (EVs) are derived from internal cellular compartments, and have potential as a diagnostic and therapeutic tool in degenerative disease associated with aging. Mesenchymal stem cells (MSCs) have become a promising tool for functional EVs production. This study investigated the efficacy of EVs and its effect on differentiation capacity. Methods: The characteristics of MSCs were evaluated by flow cytometry and stem cell differentiation analysis, and a production mode of functional EVs was scaled from MSCs. The concentration and size of EVs were quantitated by Nanoparticle Tracking Analysis (NTA). Western blot analysis was used to assess the protein expression of exosome-specific markers. The effects of MSC-derived EVs were assessed by chondrogenic and adipogenic differentiation analyses and histological observation. Results: The range of the particle size of adipose-derived stem cells (ADSCs)- and Wharton’s jelly -MSCs-derived EVs were from 130 to 150 nm as measured by NTA, which showed positive expression of exosomal markers. The chondrogenic induction ability was weakened in the absence of EVs in vitro . Interestingly, after EV administration, type II collagen, a major component in the cartilage extracellular matrix, was upregulated compared to the EV-free condition. Moreover, EVs decreased the lipid accumulation rate during adipogenic induction. Conclusion: The results indicated that the production model could facilitate production of effective EVs and further demonstrated the role of MSC-derived EVs in cell differentiation. MSC-derived EVs could be successfully used in cell-free therapy to guide chondrogenic differentiation of ADSC for future clinical applications in cartilage regeneration.

Recent Developments in Additive-Manufactured Intermetallic Compounds for Bio-Implant Applications - Po-Yuan Yeh; Jacob C. Huang; Jason S. C. Jang; Cheng-Tang Pan; Chung-Hwan Chen; Che-Hsin Lin (Journal of Medical and Biological Engineering, 2022)
Purpose This paper reviews the recent developments of two newly developed intermetallic compounds (IMCs) of metallic glasses (MGs) and high-entropy alloys (HEAs) as potential implantable biomaterials. Methods The paper commences by summarizing the fundamental properties of recently developed MGs and high-entropy alloys (HEAs). A systematic review is presented of the recent literature about the use of AM technology in fabricating MG and HEA components for biological implant applications. Results The high strength, low Young’s modulus, and excellent corrosion resistance make these IMCs good candidates as bio-implantable materials. Recent studies have shown that additive manufacturing (AM) techniques provide an advantageous route for the preparation of glassy metallic components due to their intrinsically rapid cooling rates and ability to fabricate parts with virtually no size or complexity constraints. A practical example is conducted by AM producing a porous gradient Ti-based MG spinal cage. The produced MG powders and the in vivo test results on an 18 M-old Lanyu pig confirm the feasibility of the AM technique for producing implantable IMC-based prosthesis. Conclusion The non-crystalline structure of MGs alloy and the random crystalline composition of HEAs provide unique material properties that will substantially impact the development of future implantable prostheses.

Genetic Variations and Expansion of the Blue Swimmer Crab (Portunus pelagicus) in Southeast Asia - Yu-Ming Lu; Chun-Han Shih; Po-Cheng Chen; Wei-Chieh Kao; Ying-Chou Lee; Yu-San Han; Tzong-Der Tzeng (Journal of Marine Science and Engineering, 2022)
Blue swimmer crabs (Portunus pelagicus) primarily inhabit the coastal regions of Southeast Asia. This study aimed to examine their population genetic structure, phylogeography, and historical demography by applying partial sequences to the control region in the mitochondrial DNA. The analysis focused on 6 populations comprising 166 individual samples collected from Taiwan (Kezailiao Kaohsiung (KK) and Penghu (PH)), mainland China (Xiamen (XM) and Hong Kong (HK)), Vietnam (Hanoi (VN)), and Singapore (SGP). The estimated nucleotide diversity (π) for all of the samples was 0.062, with values ranging between 0.018 (PH) and 0.045 (HK). Our study collected 116 haplotypes and classified them into lineages A and B. The XM, HK, VN, and SGP populations made up lineage A, and the PH and KK populations comprised lineage B. For each lineage, the results highlighted indications of demographic expansion. Lineage A can be traced back to the second-to-last interglacial period, while lineage B possibly originated in the last glacial period. There were significant differences in the FST values among the six populations, except for the pairs HK–XM and PH–KK. In conclusion, the phylogeography and genetic structure of P. pelagicus in Southeast Asia were potentially affected by the Pleistocene glacial cycles and human introduction. These findings further highlight the possible dispersal routes of P. pelagicus throughout Southeast Asia.

Environmental indicators combined with risk analysis to evaluate potential wildfire incidence on the Dadu Plateau in Taiwan - Chao-Yuan Lin; Pei-Ying Shieh; Shao-Wei Wu; Po-Cheng Wang; Yung-Chau Chen (Natural Hazards, 2022)
Wildfire is a common disaster in the world, and it has a considerable impact on the safety of residents and ecological disturbance. Periodic wildfires are an urgent problem to be solved. This research uses big data from relevant departments to extract environmental indicators that affect wildfires, including satellite images, meteorological observations, and field surveys and establishes a risk model for the Spatio-temporal distribution of wildfires based on risk analysis. Previous studies using Differenced Normalized Burn Ratio (dNBR) to assess fire severity and distinguish wildfire ruins did not deal with the impact of atmospheric humidity on dNBR values. In this study, an adjustable fire threshold was developed to enable dNBR to improve the accuracy of identifying wildfire locations. Regarding the temporal distribution of wildfire risks, environmental vulnerability cannot specifically reflect the frequency of actual wildfires. If the hazard degree is introduced to calculate the wildfire risk, the coefficient of determination can be increased from 0.49 to 0.79. The verification of the village boundary zone depicts that the risk analysis can effectively show the temporal and spatial distribution of wildfire hotspots. On this basis, a village-level wildfire disaster prevention strategy can be formulated.

Brain Reactions to Opening and Closing the Eyes: Salivary Cortisol and Functional Connectivity - Shen-Da Chang; Po-Chih Kuo; Karl Zilles; Tim Q. Duong; Simon B. Eickhoff; Andrew C. W. Huang; Arthur C. Tsai; Philip E. Cheng; Michelle Liou (Brain Topography, 2022)
This study empirically assessed the strength and duration of short-term effects induced by brain reactions to closing/opening the eyes on a few well-known resting-state networks. We also examined the association between these reactions and subjects’ cortisol levels. A total of 55 young adults underwent 8-min resting-state fMRI (rs-fMRI) scans under 4-min eyes-closed and 4-min eyes-open conditions. Saliva samples were collected from 25 of the 55 subjects before and after the fMRI sessions and assayed for cortisol levels. Our empirical results indicate that when the subjects were relaxed with their eyes closed, the effect of opening the eyes on conventional resting-state networks (e.g., default-mode, frontal-parietal, and saliency networks) lasted for roughly 60-s, during which we observed a short-term increase in activity in rs-fMRI time courses. Moreover, brain reactions to opening the eyes had a pronounced effect on time courses in the temporo-parietal lobes and limbic structures, both of which presented a prolonged decrease in activity. After controlling for demographic factors, we observed a significantly positive correlation between pre-scan cortisol levels and connectivity in the limbic structures under both conditions. Under the eyes-closed condition, the temporo-parietal lobes presented significant connectivity to limbic structures and a significantly positive correlation with pre-scan cortisol levels. Future research on rs-fMRI could consider the eyes-closed condition when probing resting-state connectivity and its neuroendocrine correlates, such as cortisol levels. It also appears that abrupt instructions to open the eyes while the subject is resting quietly with eyes closed could be used to probe brain reactivity to aversive stimuli in the ventral hippocampus and other limbic structures.

Investment Feasibility Analysis of Large Submersible Cage Culture in Taiwan: A Case Study of Snubnose Pompano (Trachinotus anak) and Cobia (Rachycentron canadum) - Hsun-Yu Lan; Farok Afero; Cheng-Ting Huang; Bo-Ying Chen; Po-Lin Huang; Yen-Lung Hou (Fishes, 2022)
Onshore farming for premium aquaculture is under scrutiny and criticism partially due to possible causes of adverse environmental impacts on other resource users and the surrounding environment. The best alternative to preventing or minimizing these impacts is to utilize open seawater by large submersible cage culture. The current operation in Taiwan has demonstrated that the culture operation is technically feasible but economically demanding because of high capital and operating costs. Therefore, this study conducted an economic analysis of the expansion of large submersible cage culture by selecting two premium species of snubnose pompano (Trachinotus anak) and cobia (Rachycentron canadum) and examined the profitability of large submersible cage culture investment. This study found that the current operation of four-unit cages highlighted a negative net present value and internal rate of return with a payback period of over ten and six years, respectively. Large submersible cage culture can be financially profitable when its operation unit expands from 8 to 24 units. Increasing unit cages to eight incurred a gross margin of 17.09%, BCR 1.21, with a payback period of 5.36 years. Expanding the operation to 24-unit cages was a potentially lucrative investment with a gross margin of 18.51%, BCR 1.23, PI 2.15, internal rate of return of 20.84%, and a payback period of 3.55 years. Sensitivity analyses revealed that market price and survival rate significantly impact the profitability of large submersible cage culture. Finally, it is suggested that producers could invest in 8-unit cages and maintaining the survival rate of snubnose pompano and cobia at 80% and 40%, respectively.

Relationships of multiple metals exposure, global DNA methylation, and urothelial carcinoma in central Taiwan - Hui-Tsung Hsu; Hui-Ling Lee; Hsu-Hui Cheng; Chao-Hsiang Chang; Chiu-Shong Liu; Po-Jen Hsiao; Han Chang; Chi-Shun Lien; Mu-Chi Chung; Chi-Jung Chung (Archives of Toxicology, 2022)

Bioeconomic evaluation of Eleutheronema tetradactylum farming: a case study in Taiwan - Cheng-Ting Huang; Farok Afero; Fang-Yu Lu; Bo-Ying Chen; Po-Lin Huang; Hsun-Yu Lan; Yen-Lung Hou (Fisheries Science, 2022)

Phylogeography and Genetic Structure of the Swimming Crabs Portunus sanguinolentus (Herbst, 1783) in East Asia - Yu-Ming Lu; Chun-Han Shih; Po-Cheng Chen; Wei-Chieh Kao; Ying-Chou Lee; Yu-San Han; Tzong-Der Tzeng (Journal of Marine Science and Engineering, 2022)
The three-spot swimming crab (Portunus sanguinolentus) is mainly distributed in South East Asia. An analysis of mitochondrial control region partial sequences allows us to determine the population genetic structure, phylogeography and historical demography of this species in East Asia. The seven populations, which included 110 individuals, were collected from mainland China (Shanghai, SH, Xiamen, XM and Hong Kong, HK), Taiwan (Yilan, YL, Taichung, TC, Donggang, DG) and Singapore (Singapore, SGP). The nucleotide diversity (π) of all individuals was 0.01149, with values ranging from 0.00372 (SGP) to 0.01345 (YL). In total, 90 haplotypes have been identified, which can be divided into two major lineages: lineage A consists of specimens from SH, YL, XM, TC and DG, and lineage B corresponds to specimen from SGP. From the second to the most recent interglacial period, population expansion was observed in each lineage. However, a low level of genetic differentiation was also observed in the three-spotted swimming crab, P. sanguinolentus, according to FST values. Our results suggest that several past and present habitat configurations have shaped the genetic patterns of P. sanguinolentus until now. During Pleistocene glaciations, when sea levels were low, this species may have moved along the coast from Southeast Asia to China. It first colonized the Hong Kong area during this era. After sea levels rose and shorelines receded, it subsequently spread to the coast of mainland China.

miRNA–mRNA Integrative Analysis Reveals the Roles of miRNAs in Hypoxia-Altered Embryonic Development- and Sex Determination-Related Genes of Medaka Fish - Keng Po Lai; Nathan Yi Kan Tam; Yuelong Chen; Chi Tim Leung; Xiao Lin; Chau Fong Tsang; Yin Cheung Kwok; William Ka Fai Tse; Shuk Han Cheng; Ting Fung Chan; Richard Yuen Chong Kong (Frontiers in Marine Science, 2022)
Recent studies have shown hypoxia to be an endocrine disruptor that impairs sex differentiation and reproductive function, leading to male-biased F1 populations in fish. However, the molecular mechanisms through which hypoxia alters fish sex differentiation and therefore sex ratios remain poorly understood. In order to understand the potential role of miRNAs in mediating hypoxia-altered sex determination and differentiation in fish, we conducted small RNA sequencing and transcriptome sequencing on marine medaka ( Oryzias melastigma ) embryos that were exposed to hypoxia (2.0 ± 0.2 mg O 2 L – 1) for 40 h (encompassing a critical window of sex determination). We identified dysregulated miRNAs and mRNAs in the hypoxia-exposed embryo, and bioinformatic analysis of the integrative small RNA sequencing and transcriptome sequencing results revealed hypoxia to cause alterations of genes related to embryonic development through miRNA regulation. Importantly, we have identified miRNA-mRNA pairs that were reported to play roles in gonad development (novel miR-145-col9a3 and novel miRNA-94- arid5b), in sex hormone response (novel miRNA-210-ca2, novel miRNA-106-nr2f2, nbr-miR-29c-nr4a1, and ola-miR-92b-akr1d1), and in sex characteristic development (novel miRNA-145-mns1, nle-miR-20-sord, and ipu-miR-219b-abcc8). Our findings highlighted the possible roles of miRNA–mRNA in regulation of embryonic development and sex determination in response to hypoxic stress.

Associations between lung-deposited dose of particulate matter and culture-positive pulmonary tuberculosis pleurisy - Kuan-Jen Bai; Nguyen Thanh Tung; Ta-Chih Hsiao; Tsai-Ling Chen; Kian Fan Chung; Shu-Chuan Ho; Cheng-Yu Tsai; Jen-Kun Chen; Chun-Nin Lee; Kang-Yun Lee; Chih-Cheng Chang; Tzu-Tao Chen; et al. (Environmental Science and Pollution Research, 2022)

Intramyocardial injection of human adipose-derived stem cells ameliorates cognitive deficit by regulating oxidative stress–mediated hippocampal damage after myocardial infarction - Tsung-Ming LEE; Cheng-Che LEE; Horng-Jyh HARN; Tzyy-Wen Chiou; Ming-Hsi CHUANG; Chun-Hung CHEN; Chi-Hsuan CHUANG; Po-Cheng LIN; Shinn-Zong LIN (Journal of Molecular Medicine, 2021)
Cognitive impairment is a serious side effect of post-myocardial infarction (MI) course. We have recently demonstrated that human adipose-derived stem cells (hADSCs) ameliorated myocardial injury after MI by attenuating reactive oxygen species (ROS) levels. Here, we studied whether the beneficial effects of intramyocardial hADSC transplantation can extend to the brain and how they may attenuate cognitive dysfunction via modulating ROS after MI. After coronary ligation, male Wistar rats were randomized via an intramyocardial route to receive either vehicle, hADSC transplantation (1 × 10 6 cells), or the combination of hADSCs and 3-Morpholinosydnonimine (SIN-1, a peroxynitrite donor). Whether hADSCs migrated into the hippocampus was assessed by using human-specific primers in qPCR reactions. Passive avoidance test was used to assess cognitive performance. Postinfarction was associated with increased oxidative stress in the myocardium, circulation, and hippocampus. This was coupled with decreased numbers of dendritic spines as well as a significant downregulation of synaptic plasticity consisting of synaptophysin and PSD95. Step-through latency during passive avoidance test was impaired in vehicle-treated rats after MI. Intramyocardial hADSC injection exerted therapeutic benefits in improving cardiac function and cognitive impairment. None of hADSCs was detected in rat’s hippocampus at the 3rd day after intramyocardial injection. The beneficial effects of hADSCs on MI-induced histological and cognitive changes were abolished after adding SIN-1. MI-induced ROS attacked the hippocampus to induce neurodegeneration, resulting in cognitive deficit. The remotely intramyocardial administration of hADSCs has the capacity of improved synaptic neuroplasticity in the hippocampus mediated by ROS, not the cell engraftment, after MI. Key messages Human adipose-derived stem cells (hADSCs) ameliorated injury after myocardial infarction by attenuating reactive oxygen species (ROS) levels. Intramyocardial administration of hADSCs remotely exerted therapeutic benefits in improving cognitive impairment after myocardial infarction. The improved synaptic neuroplasticity in the hippocampus was mediated by hADSC-inhibiting ROS, not by the stem cell engraftment.

Electrical Impedance Tomography Analysis Between Two Similar Respiratory System Compliance During Decremetal PEEP Titration in ARDS Patients - Po-Lan Su; Wei-Chieh Lin; Yen-Fen Ko; Kuo-Sung Cheng; Chang-Wen Chen (Journal of Medical and Biological Engineering, 2021)
Purpose The positive end-expiratory pressure (PEEP) level with best respiratory system compliance (Crs) is frequently used for PEEP selection in acute respiratory distress syndrome (ARDS) patients. On occasion, two similar best Crs (where the difference between the Crs of two PEEP levels is < 1 ml/cm H 2 O) may be identified during decremental PEEP titration. Selecting PEEP under such conditions is challenging. The aim of this study was to provide supplementary rationale for PEEP selection by assessing the global and regional ventilation distributions between two PEEP levels in this situation. Methods Eight ARDS cases with similar best Crs at two different PEEP levels were analyzed using examination-specific electrical impedance tomography (EIT) measures and airway stress index (SIaw). Five Crs were measured at PEEP values of 25 cm H 2 O (PEEP 25 ), 20 cm H 2 O (PEEP 20 ), 15 cm H 2 O (PEEP H ), 11 cm H 2 O (PEEP I ), and 7 cm H 2 O (PEEP L ). The higher PEEP value of the two PEEPs with similar best Crs was designated as PEEP upper , while the lower designated as PEEP lower . Results PEEP H and PEEP I shared the best Crs in two cases, while similar Crs was found at PEEP I and PEEP L in the remaining six cases. SIaw was higher with PEEP upper as compared to PEEP lower (1.06 ± 0.10 versus 0.99 ± 0.09, p = 0.05). Proportion of lung hyperdistension was significantly higher with PEEP upper than PEEP lower (7.0 ± 5.1% versus 0.3 ± 0.5%, p = 0.0002). In contrast, proportion of recruitable lung collapse was higher with PEEP lower than PEEP upper (18.6 ± 4.4% versus 5.9 ± 3.7%, p < 0.0001). Cyclic alveolar collapse and reopening during tidal breathing was higher at PEEP lower than PEEP upper (34.4 ± 19.3% versus 16.0 ± 9.1%, p = 0.046). The intratidal gas distribution (ITV) index was also significantly higher at PEEP lower than PEEP upper (2.6 ± 1.3 versus 1.8 ± 0.7, p = 0.042). Conclusions PEEP upper is a rational selection in ARDS cases with two similar best Crs. EIT provides additional information for the selection of PEEP in such circumstances.

RSF1 requires CEBP/β and hSNF2H to promote IL-1β-mediated angiogenesis: the clinical and therapeutic relevance of RSF1 overexpression and amplification in myxofibrosarcomas - Chien-Feng Li; Ti-Chen Chan; Cheng-I. Wang; Fu-Min Fang; Po-Chun Lin; Shih-Chen Yu; Hsuan-Ying Huang (Angiogenesis, 2021)

Detection of Vestibular Schwannoma on Triple-parametric Magnetic Resonance Images Using Convolutional Neural Networks - Tzu-Hsuan Huang; Wei-Kai Lee; Chih-Chun Wu; Cheng-Chia Lee; Chia-Feng Lu; Huai-Che Yang; Chun-Yi Lin; Wen-Yuh Chung; Po-Shan Wang; Yen-Ling Chen; Hsiu-Mei Wu; Wan-You Guo; et al. (Journal of Medical and Biological Engineering, 2021)
Purpose The first step in typical treatment of vestibular schwannoma (VS) is to localize the tumor region, which is time-consuming and subjective because it relies on repeatedly reviewing different parametric magnetic resonance (MR) images. A reliable, automatic VS detection method can streamline the process. Methods A convolutional neural network architecture, namely YOLO-v2 with a residual network as a backbone, was used to detect VS tumors from MR images. To heighten performance, T1-weighted–contrast-enhanced, T2-weighted, and T1-weighted images were combined into triple-channel images for feature learning. The triple-channel images were cropped into three sizes to serve as input images of YOLO-v2. The VS detection effectiveness levels were evaluated for two backbone residual networks that downsampled the inputs by 16 and 32. Results The results demonstrated the VS detection capability of YOLO-v2 with a residual network as a backbone model. The average precision was 0.7953 for a model with 416 × 416-pixel input images and 16 instances of downsampling, when both the thresholds of confidence score and intersection-over-union were set to 0.5. In addition, under an appropriate threshold of confidence score, a high average precision, namely 0.8171, was attained by using a model with 448 × 448-pixel input images and 16 instances of downsampling. Conclusion We demonstrated successful VS tumor detection by using a YOLO-v2 with a residual network as a backbone model on resized triple-parametric MR images. The results indicated the influence of image size, downsampling strategy, and confidence score threshold on VS tumor detection.

An Insight into the Excavation-Induced Stress Paths on Mechanical Response of Weak Interlayer Zone in Underground Cavern Under High Geostress - Shu-Qian Duan; Quan Jiang; Guo-Feng Liu; Jie-Cheng Xiong; Po Gao; Ding-Ping Xu; Ming-Yu Li (Rock Mechanics and Rock Engineering, 2021)

Delayed association of acute particulate matter 2.5 air pollution exposure with loss of complexity in cardiac rhythm dynamics: insight from detrended fluctuation analysis - Tsung-Ying Tsai; Li-Wei Lo; Shin-Huei Liu; Wen-Han Cheng; Yu-Hui Chou; Wei-Lun Lin; Yenn-Jiang Lin; Shih-Lin Chang; Yu-Feng Hu; Fa-Po Chung; Jo-Nan Liao; Tze-Fan Chao; et al. (Environmental Science and Pollution Research, 2021)

Changes in arthropod community but not plant quality benefit a specialist herbivore on plants under reduced water availability - Po-An Lin; Chia-Ming Liu; Jia-Ang Ou; Cheng-Han Sun; Wen-Po Chuang; Chuan-Kai Ho; Natsuko Kinoshita; Gary W. Felton (Oecologia, 2021)

The mechanism of EAP-EU combined impact on summer rainfall over North Asia - Po Hu; Jianbo Cheng; Guolin Feng; Muhammad Mubashar Ahmad Dogar; Zhiqiang Gong (Theoretical and Applied Climatology, 2020)

Matriptase and prostasin proteolytic activities are differentially regulated in normal and wounded skin - Shun-Cheng Chang; Chien-Ping Chiang; Chih-Hsin Lai; Po-Wen A. Du; Yu-Sin Hung; Yu-Hsuan Chen; Hui-Yu Yang; Hao-Yu Fang; Shiao-Pieng Lee; Hung-Jen Tang; Jehng-Kang Wang; Michael D. Johnson; et al. (Human Cell, 2020)

Characterization of Model Uncertainty for the Vertical Pullout Capacity of Helical Anchors in Cohesive Soils - Po Cheng; Jiang Tao Yi; Fei Liu; Jun Jie Dong (Journal of Marine Science and Engineering, 2020)
This paper conducts coupled Eulerian–Lagrangian (CEL) analysis to characterize the model uncertainty of using the cylindrical shear method (CSM) to predict the pullout capacity of helical anchors in cohesive soils. The model factor M is adopted to represent the model uncertainty, which is equal to the value of measured capacity divided by estimated solution. The model factor Mcel can be considered to be a random variable with a lognormal distribution, and its mean value and coefficient of variation (COV) are 1.02 and 0.1, respectively. Correction factor η is introduced when comparing CSM and CEL, which is found to be influenced by input parameters. The dependence on input parameters is removed by performing regression analysis and the regression equation f is obtained. Substituting the regression equation f into the original CSM constitutes the modified CSM (MCSM), and the model factor of MCSM can be modeled as a random variable with a lognormal distribution, and its mean value and COV are 1.02 and 0.13, respectively. Finally, 13 filed tests are collected to compare the prediction accuracy, the results show that the prediction error range of MCSM is mostly within 15%. The present findings might be helpful for engineers and designers to estimate the pullout capacity of helical anchors in cohesive soils more confidently.

A Near Infrared Spectroscopy System for Assessing Rehabilitation on Peripheral Arterial Occlusion Patients - Shao-Hung Lu; Cheng-Lun Tsai; Tieh-Cheng Fu; Po-Hung Chang; Shao-Ming Lu (Journal of Medical and Biological Engineering, 2020)
Purpose A near-infrared spectroscopy system was developed to evaluate peripheral arterial occlusive disease (PAOD). The wireless device can take measurements when patients are doing rehabilitation exercise. Methods Two LED modules with wavelengths of 740 nm, 808 nm and 850 nm were placed over 32 mm away from the photodiode to detect the deep backscattering from muscle tissue. The absorbance difference from the extent of tissue oxygenation was extracted using a modified Beer’s law. Measurements taken on different muscle groups were applied to determine which branch of artery is occluded. Results The changes in oxygenation of gastrocnemius and tibialis anterior muscle were recorded when PAOD patients were riding a stationary bicycle. The drop in oxygenation with exercise generally should recover within 15 min of continuing exercise. Otherwise, the artery is not capable to provide enough blood supply to the exercising muscles. Since gastrocnemius is the primary muscle used in biking exercise, the compensatory vasodilation in gastrocnemius leads to hypoperfusion in tibialis anterior muscle. Conclusion This NIRS system is helpful for detecting the changes in tissue oxygenation during exercise. Muscle hypoxia was more obvious during exercise when the artery had some degree of occlusion.

Hispidulin Inhibits Neuroinflammation in Lipopolysaccharide-Activated BV2 Microglia and Attenuates the Activation of Akt, NF-κB, and STAT3 Pathway - Chung-I Yu; Cheng-I Cheng; Ya-Fei Kang; Po-Chih Chang; In-Pin Lin; Yu-His Kuo; An-Jie Jhou; Mei-Ying Lin; Chung-Yi Chen; Chien-Hsing Lee (Neurotoxicity Research, 2020)

Joint Effect of East Asia-Pacific and Eurasian Teleconnections on the Summer Precipitation in North Asia - Po Hu; Guolin Feng; Muhammad Mubashar Dogar; Jianbo Cheng; Zhiqiang Gong (Journal of Meteorological Research, 2020)

Potential Genes Related to Levofloxacin Resistance in Mycobacterium tuberculosis Based on Transcriptome and Methylome Overlap Analysis - Hai-cheng Li; Hui-xin Guo; Tao Chen; Wei Wang; Zhu-hua Wu; Liang Chen; Hui-zhong Wu; Gao-po Xu; Xun-xun Chen; Lin Zhou (Journal of Molecular Evolution, 2020)
Drug-resistant Mycobacterium tuberculosis ( M. tuberculosis ) has become an increasingly serious public health problem and has complicated tuberculosis (TB) treatment. Levofloxacin (LOF) is an ideal anti-tuberculosis drug in clinical applications. However, the detailed molecular mechanisms of LOF-resistant M. tuberculosis in TB treatment have not been revealed. Our study performed transcriptome and methylome sequencing to investigate the potential biological characteristics of LOF resistance in M. tuberculosis H37Rv. In the transcriptome analysis, 953 differentially expressed genes (DEGs) were identified; 514 and 439 DEGs were significantly downregulated and upregulated in the LOF-resistant group and control group, respectively. The KEGG pathway analysis revealed that 97 pathways were enriched in this study. In the methylome analysis, 239 differentially methylated genes (DMGs) were identified; 150 and 89 DMGs were hypomethylated and hypermethylated in the LOF-resistant group and control group, respectively. The KEGG pathway analysis revealed that 74 pathways were enriched in this study. The overlap study suggested that 25 genes were obtained. It was notable that nine genes expressed downregulated mRNA and upregulated methylated levels, including pgi , fadE4 , php , cyp132 , pckA , rpmB1 , pfkB , acg , and ctpF , especially cyp132 , pckA , and pfkB , which were vital in LOF-resistant M. tuberculosis H37Rv. The overlapping genes between transcriptome and methylome could be essential for studying the molecular mechanisms of LOF-resistant M. tuberculosis H37Rv. These results may provide informative evidence for TB treatment with LOF.

Performance Evaluation of a New Mobile POC Lipids Analyzer - Shi-Yann Cheng; Tung-Meng Tsai; Yen-Yu Chen; Po-Jung Lai; Tai-I Chen; Tsai-Jung Chen; Chieh-Hsiao Chen (Journal of Medical and Biological Engineering, 2020)

Mobile Health for Diagnosis-PixoTest HbA1c POCT System - Shi-Yann Cheng; Tung-Meng Tsai; Yen-Yu Chen; Po-Jung Lai; Tai-I Chen; Chiung-Wen Hsu; Chieh-Hsiao Chen (Journal of Medical and Biological Engineering, 2020)

A SUITABLE DESIGN OF OUTLET TYPE FOR PADDIES IN TAIWAN BY EVALUATING THE FLOOD DETENTION EFFECT AND APPLICABILITY - Rong‐Song Chen; Yun‐Ta Cheng; Po‐Wei Huang (Irrigation and Drainage, 2019)
This study intends to enhance a paddy's flood detention effect by adjusting the outlet mechanism to mitigate flooding. Since the paddy's detention effect is an additional function, this study focuses on figuring out a suitable design by comprehensively considering the inundation duration for rice, least peak discharge for flood detention and applicability for various ridge heights. This study establishes a water balance model by utilizing the outlet's discharge coefficients and loss intensity calibrated from the field test. The study adopts the shuffled complex evolution (SCE‐UA) method to optimize the peak discharge. Based on the dimensions of the paddy ridges around the test field and a 24‐h rainfall in a 50‐year return period, both the orifice type and the overflow type perform well, with peak discharge = 0.0105 m 3 s‾¹ and peak time = 960 min. Compared with the weir type, they function well in flood detention, with peak discharge reduction = 65.9% and detention time (time span between the peak time of the weir type and that of the others) = 200 min. Despite having the best performance in flood detention, the orifice type is the least applicable due to the limitation of ridge height. The overflow type has the advantages of both the weir and the orifice types. It is the most suitable design for paddies in Taiwan in terms of applicability and flood detention effect. © 2019 John Wiley & Sons, Ltd. © 2019 John Wiley & Sons, Ltd.

Conditional Overexpression of rtn4al in Muscle of Adult Zebrafish Displays Defects Similar to Human Amyotrophic Lateral Sclerosis - Cheng-Yung Lin; Po-Hsiang Zhang; You-Jei Chen; Chia-Lun Wu; Huai-Jen Tsai (Marine Biotechnology, 2019)

The environmental feasibility of low-cost algae-based sewage treatment as a climate change adaption measure in rural areas of SADC countries - Paul J. Oberholster; Po-Hsun Cheng; B. Genthe; M. Steyn (Journal of Applied Phycology, 2019)

Engineering cyanobacteria for production of terpenoids - Po-Cheng Lin; Himadri B. Pakrasi (Planta, 2019)

Plasminogen/thrombomodulin signaling enhances VEGF expression to promote cutaneous wound healing - Tsung-Lin Cheng; Po-Ku Chen; Wei-Kai Huang; Cheng-Hsiang Kuo; Chia-Fong Cho; Kuan-Chieh Wang; Guey-Yueh Shi; Hua-Lin Wu; Chao-Han Lai (Journal of Molecular Medicine, 2018)

Iterative Frequency-Domain Response of Floating Offshore Wind Turbines with Parametric Drag - Frank Lemmer; Wei Yu; Po Wen Cheng (Journal of Marine Science and Engineering, 2018)
Methods for coupled aero-hydro-servo-elastic time-domain simulations of Floating Offshore Wind Turbines (FOWTs) have been successfully developed. One of the present challenges is a realistic approximation of the viscous drag of the wetted members of the floating platform. This paper presents a method for an iterative response calculation with a reduced-order frequency-domain model. It has heave plate drag coefficients, which are parameterized functions of literature data. The reduced-order model does not represent more than the most relevant effects on the FOWT system dynamics. It includes first-order and second-order wave forces, coupled with the wind turbine structural dynamics, aerodynamics and control system dynamics. So far, the viscous drag coefficients are usually defined as constants, independent of the load cases. With the computationally efficient frequency-domain model, it is possible to iterate the drag, such that it fits to the obtained amplitudes of oscillation of the different members. The results show that the drag coefficients vary significantly across operational load conditions. The viscous drag coefficients converge quickly and the method is applicable for concept-level design studies of FOWTs with load case-dependent drag.

Characterization and adsorption capacity of potassium permanganate used to modify activated carbon filter media for indoor formaldehyde removal - Shih-Cheng Hu; Ying-Chen Chen; Xin-Zhi Lin; Angus Shiue; Po-Hua Huang; Yen-Che Chen; Shu-Mei Chang; Chao-Heng Tseng; Bin Zhou (Environmental Science and Pollution Research, 2018)

Extension of C. elegans lifespan using the ·NO-delivery dinitrosyl iron complexes - Hsiao-Wen Huang; Yen-Hung Lin; Min-Hsuan Lin; Ya-Rong Huang; Chih-Hung Chou; Hsiao-Chin Hong; Mei-Ren Wang; Yu-Ting Tseng; Po-Chun Liao; Min-Chuan Chung; Yu-Jie Ma; Shou-Cheng Wu; et al. (JBIC Journal of Biological Inorganic Chemistry, 2018)

Expression of serine peptidase inhibitor Kunitz type 1 in differentiated thyroid cancer - Chien-Liang Liu; Po-Sheng Yang; Ming-Nan Chien; Yuan-Ching Chang; Chi-Hsin Lin; Shih-Ping Cheng (Histochemistry and Cell Biology, 2018)

Enhancement of the relationship between the winter Arctic oscillation and the following summer circulation anomalies over central East Asia since the early 1990s - Shaobo Qiao; Po Hu; Taichen Feng; Jianbo Cheng; Zixuan Han; Zhiqiang Gong; Rong Zhi; Guolin Feng (Climate Dynamics, 2018)

Schwann-Cell Autophagy, Functional Recovery, and Scar Reduction After Peripheral Nerve Repair - Po-Yen Ko; Cheng-Chang Yang; Yao-Lung Kuo; Fong-Chin Su; Tai-I Hsu; Yuan-Kun Tu; I-Ming Jou (Journal of Molecular Neuroscience, 2018)

Assessment of selected macroalgae for use in a biological hybrid system for treating sulphur in acid mine drainage (AMD) - Paul J. Oberholster; Po-Hsun Cheng; Anna-Maria Botha; Philip Hobbs; Liesl Hill (Journal of Applied Phycology, 2018)

Larger but not louder: bigger honey bee colonies have quieter combs - Michael L Smith; Po-Cheng Chen (Behavioral Ecology and Sociobiology, 2017)

G-CSF-mobilized Bone Marrow Mesenchymal Stem Cells Replenish Neural Lineages in Alzheimer’s Disease Mice via CXCR4/SDF-1 Chemotaxis - Cheng-Chun Wu; I-Fang Wang; Po-Min Chiang; Liang-Chao Wang; Che-Kun James Shen; Kuen-Jer Tsai (Molecular Neurobiology, 2017)

Numerical modeling and dynamic analysis of the 2017 Xinmo landslide in Maoxian County, China - Chao-jun Ouyang; Wei Zhao; Si-ming He; Dong-po Wang; Shu Zhou; Hui-cong An; Zhong-wen Wang; Duo-xiang Cheng (Journal of Mountain Science, 2017)

Cytoplasmic aryl hydrocarbon receptor regulates glycogen synthase kinase 3 beta, accelerates vimentin degradation, and suppresses epithelial–mesenchymal transition in non-small cell lung cancer cells - Ching-Hao Li; Chen-Wei Liu; Chi-Hao Tsai; Yi-Jen Peng; Yu-Hsuan Yang; Po-Lin Liao; Chen-Chen Lee; Yu-Wen Cheng; Jaw-Jou Kang (Archives of Toxicology, 2017)

Anti-apoptotic and Pro-survival Effects of Food Restriction on High-Fat Diet-Induced Obese Hearts - Yi-Yuan Lin; Po-Shiuan Hsieh; Yu-Jung Cheng; Shiu-Min Cheng; Chiao-nan Chen; Chih-Yang Huang; Chia-Hua Kuo; Chung-Lan Kao; Woei-Cherng Shyu; Shin-Da Lee (Cardiovascular Toxicology, 2017)

Experimental and numerical studies on the performance and surface streamlines on the blades of a horizontal-axis wind turbine - Chi-Jeng Bai; Wei-Cheng Wang; Po-Wei Chen (Clean Technologies and Environmental Policy, 2017)

Development of a fluorescence resonance energy transfer–based intracellular assay to identify novel enterovirus 71 antivirals - Wen-Wen Lu; Fang-Yen Kung; Po-An Deng; Yu-Chu Lin; Cheng-Wen Lin; Szu-Hao Kung (Archives of Virology, 2017)

Postnatal Stress Induced by Injection with Valproate Leads to Developing Emotional Disorders Along with Molecular and Cellular Changes in the Hippocampus and Amygdala - Chih-Yen Wang; Chien-Wen Cheng; Wei-Hua Wang; Po-See Chen; Shun-Fen Tzeng (Molecular Neurobiology, 2016)

Amarogentin ameliorates diabetic disorders in animal models - Ho-Shan Niu; Pin-Chun Chao; Po-Ming Ku; Chiang-Shan Niu; Kung-Shing Lee; Juei-Tang Cheng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Curcumin downregulates p38 MAPK-dependent X-ray repair cross-complement group 1 (XRCC1) expression to enhance cisplatin-induced cytotoxicity in human lung cancer cells - Chun-Liang Tung; Yi-Jun Jian; Jyh-Cheng Chen; Tai-Jing Wang; Wen-Ching Chen; Hao-Yu Zheng; Po-Yuan Chang; Kai-Sheng Liao; Yun-Wei Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Effects of 4-methylbenzylidene camphor (4-MBC) on neuronal and muscular development in zebrafish (Danio rerio) embryos - Vincent Wai Tsun Li; Mei Po Mirabelle Tsui; Xueping Chen; Michelle Nga Yu Hui; Ling Jin; Raymond H. W. Lam; Richard Man Kit Yu; Margaret B. Murphy; Jinping Cheng; Paul Kwan Sing Lam; Shuk Han Cheng (Environmental Science and Pollution Research, 2016)

Aerodynamic design and analysis of a 10 kW horizontal-axis wind turbine for Tainan, Taiwan - Chi-Jeng Bai; Po-Wei Chen; Wei-Cheng Wang (Clean Technologies and Environmental Policy, 2016)

Seasonal difference of human adenoviruses in a subtropical river basin based on 1-year monthly survey - Chi-Wei Tao; Bing-Mu Hsu; Po-Min Kao; Wen-Chien Huang; Tsui-Kang Hsu; Ying-Ning Ho; Yen-Ju Lu; Cheng-Wei Fan (Environmental Science and Pollution Research, 2016)

Sulbactam treatment for pneumonia involving multidrug-resistant Acinetobacter calcoaceticus–Acinetobacter baumannii complex - Huang-Shen Lin; Ming-Hsun Lee; Chun-Wen Cheng; Po-Chang Hsu; Hsieh-Shong Leu; Ching-Tai Huang; Jung-Jr Ye (Infectious Diseases, 2015)

Rapid detection of copper chlorophyll in vegetable oils based on surface-enhanced Raman spectroscopy - Wei-Nan Lian; Jessie Shiue; Huai-Hsien Wang; Wei-Chen Hong; Po-Han Shih; Chao-Kai Hsu; Ching-Yi Huang; Cheng-Rong Hsing; Ching-Ming Wei; Juen-Kai Wang; Yuh-Lin Wang (Food Additives & Contaminants: Part A, 2015)

Development of 8-benzyloxy-substituted quinoline ethers and evaluation of their antimicrobial activities - Po-Yee Chung; Roberto Gambari; Yi-Xin Chen; Chor-Hing Cheng; Zhao-Xiang Bian; Albert Sun-Chi Chan; Johnny Cheuk-On Tang; Polly Hang-Mei Leung; Chung-Hin Chui; Kim-Hung Lam (Medicinal Chemistry Research, 2015)

A Potential Association Between Antibiotic Abuse and Existence of Related Resistance Genes in Different Aquatic Environments - Chao-Yu Hsu; Bing-Mu Hsu; Wen-Tsai Ji; Tien-Yu Chang; Po-Min Kao; Shao-Feng Tseng; Tsung-Yu Shen; Feng-Cheng Shih; Cheng-Wei Fan; Jorn-Hon Liu (Water, Air, & Soil Pollution, 2015)

The Association of RAB18 Gene Polymorphism (rs3765133) with Cerebellar Volume in Healthy Adults - Chih-Ya Cheng; Albert C. Yang; Chu-Chung Huang; Mu-En Liu; Ying-Jay Liou; Jaw-Ching Wu; Shih-Jen Tsai; Ching-Po Lin; Chen-Jee Hong (The Cerebellum, 2014)

Minocycline accelerates hypoxia-inducible factor-1 alpha degradation and inhibits hypoxia-induced neovasculogenesis through prolyl hydroxylase, von Hippel–Lindau-dependent pathway - Ching-Hao Li; Po-Lin Liao; Ya-Ting Yang; Shih-Hsuan Huang; Cheng-Hui Lin; Yu-Wen Cheng; Jaw-Jou Kang (Archives of Toxicology, 2013)

Identification and quantitative detection of Legionella spp. in various aquatic environments by real-time PCR assay - Po-Min Kao; Min-Che Tung; Bing-Mu Hsu; Yi-Chou Chiu; Cheng-Yu She; Shu-Min Shen; Yu-Li Huang; Wen-Chien Huang (Environmental Science and Pollution Research, 2013)

Glycogen synthase kinase-3β inactivation is an intracellular marker and regulator for endotoxemic neutrophilia - Tsan-Tzu Yang; Chia-Ling Chen; Wei-Chieh Lin; Yee-Shin Lin; Po-Chun Tseng; Chia-Yuan Hsieh; Yu-Hong Chen; Wei-Ching Huang; Cheng-Chieh Tsai; Chi-Yun Wang; Chi-Chang Shieh; Chiou-Feng Lin (Journal of Molecular Medicine, 2013)

Comparison of MODIS land surface temperature and ground-based observed air temperature in complex topography - Yen-Jen Lai; Ching-Feng Li; Po-Hsiung Lin; Tsong-Hue Wey; Cheng-Sheng Chang (International Journal of Remote Sensing, 2012)

Effect of Long-Term Vinasse Application on Physico-chemical Properties of Sugarcane Field Soils - Ze-Pu Jiang; Yang-Rui Li; Guang-Po Wei; Qing Liao; Tian-Ming Su; Yan-Cheng Meng; Hai-Ying Zhang; Chang-Yan Lu (Sugar Tech, 2012)

Niacin improves ischemia-induced neovascularization in diabetic mice by enhancement of endothelial progenitor cell functions independent of changes in plasma lipids - Po-Hsun Huang; Chih-Pei Lin; Chao-Hung Wang; Chia-Hung Chiang; Hsiao-Ya Tsai; Jia-Shiong Chen; Feng-Yen Lin; Hsin-Bang Leu; Tao-Cheng Wu; Jaw-Wen Chen; Shing-Jong Lin (Angiogenesis, 2012)

Development of a simple chromatographic method for distinguishing between two easily confused species, Hedyotis diffusa and Hedyotis corymbosa - Clara B.S. Lau; Ling Cheng; Bobby W.H. Cheng; Grace G.L. Yue; Eric C.W. Wong; Ching-Po Lau; Ping-Chung Leung; Kwok-Pui Fung (Natural Product Research, 2012)

Occurrence of diarrheagenic Escherichia coli genes in raw water of water treatment plants - Shih-Wei Huang; Bing-Mu Hsu; Yen-Jui Su; Dar-Der Ji; Wei-Chen Lin; Jyh-Larng Chen; Feng-Cheng Shih; Po-Min Kao; Yi-Chou Chiu (Environmental Science and Pollution Research, 2012)

Erratum to: Genetic variation in the carbonyl reductase 3 gene confers risk of type 2 diabetes and insulin resistance: a potential regulator of adipogenesis - Yi-Cheng Chang; Pi-Hua Liu; Yun-Chih Tsai; Yen-Feng Chiu; Shyang-Rong Shih; Low-Tone Ho; Wen-Jane Lee; Chieh-Hua Lu; Thomas Quertermous; J. David Curb; Wei-Jei Lee; Po-Chu Lee; et al. (Journal of Molecular Medicine, 2012)

Genetic variation in the carbonyl reductase 3 gene confers risk of type 2 diabetes and insulin resistance: a potential regulator of adipogenesis - Yi-Cheng Chang; Pi-Hua Liu; Yun-Chih Tsai; Yen-Feng Chiu; Shyang-Rong Shih; Low-Tone Ho; Wen-Jane Lee; Chieh-Hua Lu; Thomas Quertermous; J. David Curb; Wei-Jei Lee; Po-Chu Lee; et al. (Journal of Molecular Medicine, 2012)

A Decade of Experience: Cryptococcus gattii in British Columbia - Karen H. Bartlett; Po-Yan Cheng; Colleen Duncan; Eleni Galanis; Linda Hoang; Sarah Kidd; Min-Kuang Lee; Sally Lester; Laura MacDougall; Sunny Mak; Muhammad Morshed; Marsha Taylor; et al. (Mycopathologia, 2012)

Oxidative stress in greater duckweed (Spirodela polyrhiza) caused by long-term NaCl exposure - In-Hwa Chang; Kai-Teng Cheng; Po-Chuan Huang; Yen-Yu Lin; Lee-Ju Cheng; Tai-Sheng Cheng (Acta Physiologiae Plantarum, 2012)

Identification of a small-molecule inhibitor of dengue virus using a replicon system - Yu-Chen Hsu; Nai-Chi Chen; Po-Chiang Chen; Chun-Chung Wang; Wei-Chieh Cheng; Huey-Nan Wu (Archives of Virology, 2012)

Molecular cloning and heterologous expression of an acid stable xylanase gene from Alternaria sp. HB186 - Liangwei Mao; Po Meng; Cheng Zhou; Lixin Ma; Guimin Zhang; Yanhe Ma (World Journal of Microbiology and Biotechnology, 2012)

Polycyclic aromatic hydrocarbons in household dust near diesel transport routes - Chung-Yih Kuo; Heng-Chun Chen; Fang-Ching Cheng; Li-Ru Huang; Po-Shan Chien; Jing-Ya Wang (Environmental Geochemistry and Health, 2012)

Chemical modification and anticancer effect of prenylated flavanones from Taiwanese propolis - Chia-Nan Chen; Che-Jen Hsiao; Shoei-Sheng Lee; Jih-Hwa Guh; Po-Cheng Chiang; Chih-Chiang Huang; Wei-Jan Huang (Natural Product Research, 2012)

Rilmenidine improves hepatic steatosis through p38-dependent pathway to higher the expression of farnesoid X receptor - Po-Sheng Yang; Hung-Tsung Wu; Hsien-Hui Chung; Chun-Ta Chen; Chin-Wen Chi; Ching-Hua Yeh; Juei-Tang Cheng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

Evaluation of the optimal strategy for ex situ bioremediation of diesel oil-contaminated soil - Ta-Chen Lin; Po-Tsen Pan; Chiu-Chung Young; Jo-Shu Chang; Tsung-Chung Chang; Sheng-Shung Cheng (Environmental Science and Pollution Research, 2011)

Inorganic arsenic causes cell apoptosis in mouse cerebrum through an oxidative stress-regulated signaling pathway - Cheng Chien Yen; Tsung Jung Ho; Chin Ching Wu; Chun Fang Chang; Chin Chuan Su; Ya Wen Chen; Tzyy Rong Jinn; Tien Hui Lu; Po Wen Cheng; Yi Chang Su; Shing Hwa Liu; Chun Fa Huang (Archives of Toxicology, 2011)

Insulin-like growth factor 1 mediates 5-fluorouracil chemoresistance in esophageal carcinoma cells through increasing survivin stability - Hsien-Chia Juan; Hsin-Ting Tsai; Po-Hao Chang; Chi-Ying F. Huang; Cheng-Po Hu; Fen-Hwa Wong (Apoptosis, 2011)

Cancer risks from betel quid chewing beyond oral cancer: a multiple-site carcinogen when acting with smoking - Chi Pang Wen; Min Kuang Tsai; Wen Shen Isabella Chung; Hui Ling Hsu; Yen Chen Chang; Hui Ting Chan; Po Huang Chiang; Ting-Yuan David Cheng; Shan Pou Tsai (Cancer Causes & Control, 2010)

Secular trend of genome types of respiratory adenovirus type 3 during 1983–2005: a study from Taiwan - Yung-Cheng Lin; Kuei-Hsiang Lin; Guan-Ming Ke; Min-Sheng Lee; Pei-Chin Lin; Hsin-Fu Liu; Li-Ching Hsu; Po-Liang Lu (Archives of Virology, 2010)

Tunicamycin induces resistance to camptothecin and etoposide in human hepatocellular carcinoma cells: role of cell-cycle arrest and GRP78 - Jui-Ling Hsu; Po-Cheng Chiang; Jih-Hwa Guh (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Integrating Social Marketing into Sustainable Resource Management at Padre Island National Seashore: An Attitude-Based Segmentation Approach - Po-Hsin Lai; Michael G. Sorice; Sanjay K. Nepal; Chia-Kuen Cheng (Environmental Management, 2009)

Simultaneously monitoring the particle size distribution, morphology and suspended solids concentration in wastewater applying digital image analysis (DIA) - Ruey-Fang Yu; Ho-Wen Chen; Wen-Po Cheng; Mei-Ling Chu (Environmental Monitoring and Assessment, 2009)

Elucidation of susceptible factors to endoplasmic reticulum stress-mediated anticancer activity in human hepatocellular carcinoma - Po-Cheng Chiang; Jui-Ling Hsu; Ting-Chun Yeh; Shiow-Lin Pan; Jih-Hwa Guh (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

Prevention of TGF-β-induced apoptosis by interlukin-4 through Akt activation and p70S6K survival signaling pathways - Sue-Jane Lin; Chungming Chang; Ah-Kau Ng; Shu-Han Wang; Jia-Je Li; Cheng-po Hu (Apoptosis, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Atmosphic pollutants study of particles ionic species during high wind speed (>7 m s-1) near Taiwan strait in central Taiwan from 2004 to 2005 - Guor-Cheng Fang; Yuh-Shen Wu; Wen-Jhy Lee; Chi-Kwong Lin; Chung-Po Lin (Environmental Monitoring and Assessment, 2007)

Measurements of Wastewater True Color by 4/6 Wavelength Methods and Artificial Neural Network - Ruey-Fang Yu; Ho-Wen Chen; Wen-Po Cheng; Mei-Ling Chu (Environmental Monitoring and Assessment, 2006)

Transgenic tomato plants expressing an Arabidopsis thionin (Thi2.1) driven by fruit-inactive promoter battle against phytopathogenic attack - Yuan-Li Chan; Venkatesh Prasad; Sanjaya; Kuei Hung Chen; Po Chang Liu; Ming-Tsair Chan; Chiu-Ping Cheng (Planta, 2005)

Evaluating the Efficiency of Coagulation in the Removal of Dissolved Organic Carbon from Reservoir Water using Fluorescence and Ultraviolet Photometry - Wen Po Cheng; Fung Hwa Chi; Ruey Fang Yu (Environmental Monitoring and Assessment, 2004)

Cadmium-induced ectopic apoptosis in zebrafish embryos - Po Chan; Shuk Cheng (Archives of Toxicology, 2003)